Sheet containing composite material of polymer and hexagonal boron nitride particles and method for producing same

By ensuring their high-content hexagonal boron nitride plate-like particles in polymer materials and ensuring their high directional positioning through specific manufacturing methods, the development problems of high-thermal conductivity and low-conductivity multilayer materials in the prior art are solved, and materials with high thickness directional thermal conductivity and good dielectric properties are achieved.

JP2025509872APending Publication Date: 2025-04-113M INNOVATIVE PROPERTIES CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024555896
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-24
Filing Date
2023-03-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

It is difficult to develop multilayer materials with high thermal conductivity, low electrical conductivity and low dielectric loss in the prior art, especially in the application of 5G technology, with the increasing demand for high-thickness-direction thermal conductivity materials.

Method used

A polymer material containing plate-like particles of more than 70% by weight hexagonal boron nitride (h-BN) is used and a thin film is prepared by specific manufacturing methods such as forming a suspension and using a phase separation process to ensure high directional positioning of the h-BN particles in the material.

Benefits of technology

It has achieved multi-layer materials with thermal conductivity of more than 12 W/m·K in high thickness directions, and has good dielectric properties, including low dielectric constant and low dielectric loss, suitable for applications such as 5G technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509872000001_ABST
    Figure 2025509872000001_ABST
Patent Text Reader

Abstract

The present disclosure relates to a sheet comprising a composite material comprising a polymer and hexagonal boron nitride particles, the hexagonal boron nitride particles comprising platelet-shaped hexagonal boron nitride particles, the platelet-shaped hexagonal boron nitride particles being oriented in a direction perpendicular to the direction of the plane of the sheet, the composite material comprising at least 70 weight percent of the hexagonal boron nitride particles based on the total weight of the composite material, and the sheet having a through thickness thermal conductivity of greater than 12 W / m×K. The present disclosure further relates to a method of making the sheet.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present disclosure relates to a sheet comprising a composite material comprising a polymer and hexagonal boron nitride particles, wherein the hexagonal boron nitride particles comprise platelet-shaped hexagonal boron nitride particles oriented in a direction perpendicular to the direction of the plane of the sheet. [Background technology]

[0002] Thermally conductive polymer compounds are used in thermal management solutions. The demand for thermally conductive and electrically insulating polymer materials is increasing for electronic devices such as mobile devices, LED technology, electric vehicles, and 5G technology. To improve the performance of these materials, their thermal conductivity must be increased. To achieve this, thermally conductive fillers such as boron nitride, alumina, aluminum nitride, silicon carbide, silicon nitride, magnesium oxide, or minerals are used. Increasing the amount of thermally conductive filler added can achieve higher values ​​for thermal conductivity. The maximum filler loading in a compound typically limits the achievable thermal conductivity.

[0003] 5G technology applications require materials with high thermal conductivity, electrical insulation, and low permittivity (i.e., low dielectric constant), and low dissipation factor. In many 5G applications, these thermal interface materials are required in the form of thin films or sheets. In many cases, it is desired that the thermal conductivity of these films or sheets be as high as possible in the direction perpendicular to the plane of the film, i.e., high through-thickness thermal conductivity is required.

[0004] US Patent Application Publication No. 2010 / 0200801(A1) discloses a thermal interface material comprising a base matrix containing a polymer and 5% to 90% by weight, preferably 20% to 60% by weight, of a boron nitride filler having a platelet structure, wherein the platelet structure of the boron nitride particles provides a thermal interface material having a thermal conductivity of at least 1 W / m *The thermal interface material is substantially aligned with the thermal interface material so as to have a bulk thermal conductivity of 1000 K. The thermal interface material is extruded into a sheet. As a second step, the sheet may be laminated, pressed, cured, and sliced ​​in a direction perpendicular to the lamination direction, or the sheet may be compressed and rolled into a roll, cured, and sliced ​​in a direction perpendicular to the rolling direction into a plurality of circular pads.

[0005] WO 2019 / 097445 A1 discloses a polymer matrix composite including a porous polymer network and a plurality of thermally conductive particles dispersed within the polymer network structure.

[0006] There is a need for thermally conductive, electrically insulating thermal interface materials that have high through-thickness thermal conductivity and good dielectric properties, i.e., low dielectric constant and low dissipation factor.

[0007] As used herein, "a," "an," "the," "at least one," and "one or more" are used interchangeably. The term "comprising" is also intended to include the terms "consisting essentially of" and "consisting of." Summary of the Invention

[0008] In a first aspect, the present disclosure relates to a sheet comprising a composite material comprising a polymer and hexagonal boron nitride particles, wherein the hexagonal boron nitride particles comprise platelet-shaped hexagonal boron nitride particles, the platelet-shaped hexagonal boron nitride particles being oriented in a direction perpendicular to the direction of the plane of the sheet, the composite material comprising at least 70 weight percent hexagonal boron nitride particles, based on the total weight of the composite material, and the sheet having a through thickness thermal conductivity greater than 12 W / m×K.

[0009] In another aspect, the present disclosure also provides a method for manufacturing a sheet as disclosed herein, comprising: providing hexagonal boron nitride particles comprising a polymer, a solvent, and platelet-shaped hexagonal boron nitride particles; combining a polymer, a solvent, and hexagonal boron nitride particles to form a suspension of hexagonal boron nitride particles in a polymer solvent solution, wherein the polymer in the polymer solvent solution has a melting point and the solvent has a boiling point, and the step of combining the polymer, the solvent, and the hexagonal boron nitride particles is performed at a temperature above the melting point of the polymer in the polymer solvent solution and below the boiling point of the solvent; forming the suspension into a film, the platelet-shaped hexagonal boron nitride particles being oriented in a direction parallel to the plane of the film; Inducing phase separation of the polymer from the solvent; removing at least a portion of the solvent from the film to obtain a porous film; Optionally, compressing the porous film to obtain a densified film; laminating multiple films, either porous or densified, one after the other to obtain a film laminate; pressing the film laminate to obtain a bonded film laminate; and c) slicing a sheet from the bonded film stack in a direction perpendicular to the plane of the laminated film layers.

[0010] In another aspect, the present disclosure also provides a method for manufacturing a sheet as disclosed herein, comprising: providing hexagonal boron nitride particles comprising a polymer, a solvent, and platelet-shaped hexagonal boron nitride particles; combining a polymer, a solvent, and hexagonal boron nitride particles to form a slurry, the slurry being a suspension of polymer and hexagonal boron nitride particles in a solvent, the polymer having a melting point and the solvent having a boiling point, and the step of combining the polymer, the solvent, and the hexagonal boron nitride particles is performed at a temperature below the melting point of the polymer and below the boiling point of the solvent; forming the slurry into a film, wherein the platelet-shaped hexagonal boron nitride particles are oriented in a direction parallel to the plane of the film; heating the film in an environment that retains at least 90 weight percent of the solvent in the film, based on the weight of the solvent in the film, to solubilize at least 50 weight percent of the polymer in the solvent, based on the total weight of the polymer; Inducing phase separation of the polymer from the solvent; removing at least a portion of the solvent from the film to obtain a porous film; Optionally, compressing the porous film to obtain a densified film; laminating multiple films, either porous or densified, one after the other to obtain a film laminate; pressing the film laminate to obtain a bonded film laminate; and c) slicing a sheet from the bonded film stack in a direction perpendicular to the plane of the laminated film layers.

[0011] The sheets disclosed herein contain highly oriented boron nitride platelet-shaped particles and, as a result, have highly anisotropic properties, particularly highly anisotropic thermal conductivity properties.

[0012] The films disclosed herein contain boron nitride platelet-shaped particles oriented perpendicular to the plane of the sheet and have high through-thickness thermal conductivity.

[0013] The sheets disclosed herein have high through-thickness thermal conductivity, allowing for faster and more efficient heat removal. Compared to other boron nitride filled polymer sheets, the sheets disclosed herein have a through-thickness thermal conductivity that is higher than the in-plane thermal conductivity.

[0014] In addition, the sheets disclosed herein have good dielectric properties, specifically low dielectric constant and low dissipation factor.

[0015] Typically, the sheets disclosed herein do not include silicone.

[0016] As used herein, "phase separation" refers to a process in which particles are uniformly dispersed in a homogeneous polymer-solvent solution that is converted (e.g., by a change in temperature or solvent concentration) into a continuous three-dimensional composite, i.e., a polymer-matrix composite. In the second method disclosed herein, phase separation is achieved by solvent-induced phase separation (SIPS) using a wet or dry process, or by a thermally induced phase separation (TIPS) process. In the second method disclosed herein, the desired article is formed before the polymer is miscible with the solvent, and the phase separation is a thermally induced phase separation process.

[0017] As used herein, "miscible" refers to the ability of substances to mix in all proportions (i.e., completely dissolve in each other at any concentration) to form a solution; for some solvent-polymer systems, heat may be required to make the polymer miscible with the solvent. In contrast, substances are immiscible if they do not form a solution in significant proportions. For example, butanone is highly soluble in water, but these two solvents are not miscible because they are not soluble in all proportions.

[0018] Typically, the maximum particle loading achievable in conventional particle-filled composites (high-density polymer films, adhesives, etc.) is no more than about 40-60 volume %, based on the volume of particles and binder. Incorporating particles greater than 60 volume % into conventional particle-filled composites is typically not achievable because such high particle-loading materials cannot be processed by coating or extrusion methods and / or the resulting composites would be too brittle. Conventional composites also typically completely encapsulate the particles with binder, which prevents access to the particle surfaces and minimizes possible particle-to-particle contact. Because the thermal conductivity of thermally conductive particle-filled composites typically increases with particle loading, higher particle loadings are desirable. Surprisingly, the high levels of solvent and phase-separated morphology achieved by the methods described herein allow for relatively high particle loadings with relatively small amounts of high molecular weight binder. Without being bound by theory, it is believed that another advantage of the composite embodiments described herein is that the particles are not completely coated by the binder, which allows a high degree of particle surface contact without masking due to the porous nature of the binder. Compression of the film significantly enhances particle-to-particle contact. [Brief explanation of the drawings]

[0019] The present disclosure will be described in more detail below based on the drawings.

[0020] [Figure 1a] 1 shows a scanning electron micrograph of a cross section of a sheet disclosed herein. [Figure 1b] 1 shows a scanning electron micrograph of a cross section of a sheet disclosed herein. [Figure 2] 1A-1C show schematic diagrams of the lamination and slicing steps of the method for manufacturing sheets disclosed herein. DETAILED DESCRIPTION OF THE INVENTION

[0021] The sheet disclosed herein comprises a composite material including hexagonal boron nitride particles, including platelet-shaped hexagonal boron nitride particles, which are also sometimes referred to as flake-shaped or scale-shaped hexagonal boron nitride particles.

[0022] The platelet-shaped hexagonal boron nitride particles have basal planes that are oriented perpendicular to the plane of the sheet. In other words, in the sheets disclosed herein, the platelet-shaped hexagonal boron nitride particles are oriented in a direction perpendicular to the plane of the sheet.

[0023] The orientation perpendicular to the plane of the sheet was demonstrated by scanning electron microscopy and X-ray diffraction measurements, which showed that the hexagonal boron nitride particles in the composite were oriented perpendicular to the plane of the sheet.

[0024] Typically, at least 50 weight percent of the hexagonal boron nitride particles are platelet-shaped hexagonal boron nitride particles, based on the total weight of the hexagonal boron nitride particles. Preferably, at least 80 weight percent of the hexagonal boron nitride particles are platelet-shaped hexagonal boron nitride particles, based on the total weight of the hexagonal boron nitride particles. It is also possible for all hexagonal boron nitride particles to be platelet-shaped. Some or even all of the platelet-shaped hexagonal boron nitride particles may be aggregated into boron nitride aggregates. The platelet-shaped hexagonal boron nitride particles may also be non-aggregated.

[0025] The sheet disclosed herein comprises a composite material including a polymer. In some embodiments, the polymer may be selected from the group consisting of polyurethane, polyester, polyamide, polyether, polycarbonate, polyimide, polysulfone, polyethersulfone, polyphenylene oxide, polyacrylate, polymethacrylate, polyacrylonitrile, polyolefin, styrene, styrene-based copolymer, styrene-based copolymer, chlorinated polymer, fluorinated polymer, copolymer of ethylene and chlorotrifluoroethylene, and combinations thereof. The styrene-based copolymer may be a styrene-based random copolymer or a styrene-based block copolymer. The polyolefin may be ultra-high molecular weight polyethylene (UHMWPE) or polypropylene.

[0026] The polymer may comprise, consist essentially of, or consist of at least one thermoplastic polymer. Exemplary thermoplastic polymers include polyurethanes, polyesters (e.g., polyethylene terephthalate, polybutylene terephthalate, and polylactic acid), polyamides (e.g., nylon 6, nylon 6,6, nylon 12, and polypeptides), polyethers (e.g., polyethylene oxide and polypropylene oxide), polycarbonates (e.g., bisphenol-A-polycarbonate), polyimides, polysulfones, polyethersulfones, polyphenylene oxides, polyacrylates (e.g., thermoplastic polymers formed from the addition polymerization of monomers containing acrylate functionality), polymethacrylates (e.g., Thermoplastic polymers include those formed from the addition polymerization of monomers containing methacrylate functionality, polyolefins (e.g., polyethylene and polypropylene), styrene and styrenic random and block copolymers, chlorinated polymers (e.g., polyvinyl chloride), fluorinated polymers (e.g., polyvinylidene fluoride; copolymers of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride; copolymers of ethylene, tetrafluoroethylene, and hexafluoropropylene; and polytetrafluoroethylene), and copolymers of ethylene and chlorotrifluoroethylene. In some embodiments, the thermoplastic polymer includes a homopolymer or a copolymer (e.g., a block copolymer or a random copolymer). In some embodiments, the thermoplastic polymer comprises a mixture of at least two thermoplastic polymers (e.g., a mixture of polyethylene and polypropylene, or a mixture of polyethylene and polyacrylate). In some embodiments, the thermoplastic polymer can be at least one of polyethylene (e.g., ultra-high molecular weight polyethylene), polypropylene (e.g., ultra-high molecular weight polypropylene), polylactic acid, poly(ethylene-co-chlorotrifluoroethylene), and polyvinylidene fluoride. In some embodiments, the thermoplastic polymer is a single thermoplastic polymer (i.e., not a mixture of at least two thermoplastic polymers).In some embodiments, the thermoplastic polymer consists essentially of or consists of polyethylene (eg, ultra-high molecular weight polyethylene).

[0027] In some embodiments, the thermoplastic polymers used to make the sheet composites disclosed herein are particles having a particle size of less than 1000 micrometers (in some embodiments, in the range of 1 to 10, 10 to 30, 10 to 50, 30 to 100, 10 to 200, 10 to 500, 100 to 200, 200 to 500, 500 to 1000 micrometers).

[0028] In some embodiments, the polymers used to make the composite sheets disclosed herein have a molecular weight of 5×10 4 ~1×10 7 g / mol range (in some embodiments, 1×10 6 ~8×10 6 , 2 × 10 6 ~6×10 6 , or even 2×10 6 ~5×10 6The thermoplastic polymer has a number average molecular weight in the range of 1000 to 2000 g / mol. For purposes of this disclosure, number average molecular weight can be measured by techniques known in the art, such as gel permeation chromatography (GPC). GPC can be performed in a suitable solvent for the thermoplastic polymer with the use of narrow molecular weight distribution polymer standards (e.g., narrow molecular weight distribution polystyrene standards). Thermoplastic polymers are generally characterized as being partially crystalline and exhibit a melting point. In some embodiments, the thermoplastic polymer can have a melting point in the range of 120 to 350°C (in some embodiments, in the range of 120 to 300, 120 to 250, or even 120 to 200°C). The melting point of a thermoplastic polymer can be measured by techniques known in the art, such as measuring the onset temperature in a differential scanning calorimetry (DSC) test performed on a 5 to 10 mg sample at a heating scan rate of 10°C / min while the sample is under a nitrogen atmosphere.

[0029] In some embodiments, the polymers used to make the composite sheets disclosed herein have a molecular weight of 5×10 4 ~1×10 7 g / mol range (in some embodiments, 1×10 6 ~8×10 6 , 2 × 10 6 ~6×10 6 , or even 2×10 6 ~5×10 6 The polyethylene is an ultra-high molecular weight polyethylene (UHMWPE) with a number average molecular weight in the range of 1000 g / mol.

[0030] The hexagonal boron nitride particles are dispersed in a polymer, i.e., the polymer is a matrix material for the hexagonal boron nitride particles. The hexagonal boron nitride particles have direct particle-to-particle contact in the composite, i.e., continuous pathways of thermally conductive hexagonal boron nitride particles are formed in the composite. The direct particle-to-particle contact and continuous pathways of thermally conductive hexagonal boron nitride particles are evidenced by the high through-thickness thermal conductivity of the sheet composite.

[0031] The degree of orientation of the platelet-shaped hexagonal boron nitride particles in the film can be characterized by an orientation index measured on a sheet sample. Hexagonal boron nitride with an isotropic orientation of the platelet-shaped hexagonal boron nitride particles, and therefore no preferred orientation, has an orientation index of 1. For platelet-shaped hexagonal boron nitride particles oriented parallel to the plane of the sheet, the orientation index decreases with the degree of parallel orientation in the sheet sample and has a value less than 1. For platelet-shaped hexagonal boron nitride particles oriented perpendicular to the plane of the sheet, the orientation index increases with the degree of perpendicular orientation in the sheet sample and has a value greater than 1. As used herein, "platelet-shaped hexagonal boron nitride particles oriented perpendicular to the plane of the sheet" should be understood to mean an orientation index greater than 4.0. As used herein, "platelet-shaped hexagonal boron nitride particles oriented parallel to the plane of the sheet" should be understood to mean an orientation index of up to 0.5.

[0032] The orientation index of the sheets disclosed herein is greater than 4.0. The orientation index of the sheets may be at least 4.5, or at least 5, or at least 6, or at least 7, or at least 8, or at least 10. Preferably, the orientation index of the sheets is at least 6.

[0033] The orientation index is determined by X-ray diffraction. To do this, the ratio of the intensities of the (100) and (002) reflections of hexagonal boron nitride (hBN) measured in the X-ray diffractogram of a sheet sample is determined and divided by the corresponding ratio for an ideal, unoriented, i.e., isotropic hBN sample. This ideal ratio, which can be determined from the International Centre for Diffraction Data (ICDD) data (2020) Powder Diffraction Pattern (PDF) #01-073-2095, is 0.147. The theoretical peak positions for the (002) and (100) reflections are 26.7 degrees and 41.6 degrees, respectively. The peak intensities of the (002) and (100) reflections are measured from the peak areas at these positions. The orientation index (OI) can be determined from the following equation:

number

[0034] The composite material comprises at least 70 weight percent hexagonal boron nitride particles, based on the total weight of the composite material.

[0035] The composite may comprise at least 80, or at least 85, or at least 90, or more than 90, or at least 91, or at least 92, or at least 93, or at least 94, or at least 95, or at least 96 weight percent hexagonal boron nitride particles, based on the total weight of the composite.

[0036] The composite may comprise 70 to 98, or 80 to 98, or 85 to 98, or 90 to 98, or greater than 90 to 98, or 91 to 98, or 92 to 98, or 93 to 98, or 94 to 98, or 95 to 98, or 96 to 98 weight percent hexagonal boron nitride particles, based on the total weight of the composite.

[0037] The composite may include at least 2 weight percent polymer, based on the total weight of the composite. The composite may include up to 30, or up to 20 weight percent polymer, based on the total weight of the composite. The composite may include 2 to 30, or 2 to 20, or 2 to 15, or 2 to 10, or 2 to 9, or 2 to 8, or 2 to 7, or 2 to 6, or 2 to 5, or 2 to 4 weight percent polymer, based on the total weight of the composite.

[0038] The sheets disclosed herein have a thickness-wise thermal conductivity of greater than 12 W / m×K. The thickness-wise thermal conductivity of the sheet may be at least 15 W / m×K, or at least 18 W / m×K, or at least 20 W / m×K, or at least 25 W / m×K, or at least 30 W / m×K, or at least 35 W / m×K, or at least 40 W / m×K, or at least 45 W / m×K, or at least 50 W / m×K. The thickness-wise thermal conductivity may be greater than 12 W / m×K to 25 W / m×K, or greater than 12 to 65 W / m×K, or 15 W / m×K to 25 W / m×K, or 15 W / m×K to 65 W / m×K, or 20 W / m×K to 65 W / m×K, or 30 to 65 W / m×K, or 40 W / m×K to 65 W / m×K.

[0039] The through-thickness thermal conductivity of the sheet is higher than the in-plane thermal conductivity of the sheet. Typically, the ratio of the through-thickness thermal conductivity to the in-plane thermal conductivity of the sheet is at least 2, and may be at least 3, or at least 4, or at least 5.

[0040] Through-thickness thermal conductivity of a sheet can be measured using laser flash analysis per ASTM E1461(2013). Through-thickness thermal conductivity can also be measured according to ASTM D-5470-17 (Standard Test Method for Thermal Interface Materials). Through-thickness thermal conductivity can be measured on a sheet sample.

[0041] The in-plane thermal conductivity of the sheet may be at least 2 W / m×K. The in-plane thermal conductivity of the sheet may be measured using laser flash analysis according to ASTM E1461(2013).

[0042] The composite material contained in the sheet disclosed herein may be electrically insulating. The composite material contained in the sheet has an electrical resistivity of at least 1×10 10 It may be Ω×m.

[0043] The average particle size (d 50 ) may be 0.5 to 500 μm, or 3 to 500 μm.

[0044] The average particle size (d 50 ) may be 0.5 to 100 μm, or 3 to 100 μm.

[0045] Preferably, the average particle size (d 50 ) is at least 5 μm, more preferably at least 8 μm. In some embodiments, the average particle size (d 50 ) is 5 to 50 μm, or 5 to 30 μm, or 8 to 30 μm, or 30 to 60 μm, or 40 to 50 μm, or 8 to 15 μm, or 10 to 12 μm. 50 ) can be measured by laser diffraction.

[0046] The average aspect ratio of the platelet-shaped hexagonal boron nitride particles is typically at least 5. The aspect ratio is the ratio of the diameter to the thickness of the platelet-shaped hexagonal boron nitride particles. As used herein, the platelet-shaped hexagonal boron nitride particles are also referred to as boron nitride platelets. The aspect ratio of the boron nitride platelets may be at least 10, or at least 15, or at least 20. The average aspect ratio of the boron nitride platelets may also be up to 40, or up to 100. The average aspect ratio of the boron nitride platelets may be 7 to 20, or 20 to 40, or 7 to 40, or 10 to 40, or 50 to 100, or 5 to 500. Typically, the average aspect ratio of the boron nitride platelets is at most 500. The average aspect ratio can be measured by scanning electron microscopy (SEM) by determining the aspect ratio of 20 particles and calculating the average of the 20 individual values ​​determined for aspect ratio. The aspect ratio of individual boron nitride platelets is determined by measuring the diameter and thickness of the boron nitride platelets and calculating the ratio of diameter to thickness. The required magnification of the SEM image used to measure the diameter and thickness of the boron nitride platelets depends on the size of the platelets. The magnification should be at least 1000x, preferably at least 2000x. Where appropriate, i.e., for average particle sizes (d 50 For smaller platelets with 5000x magnification, a magnification of 5000x should be used.

[0047] The hexagonal boron nitride particles may comprise aggregates of primary particles of hexagonal boron nitride, the primary particles comprising platelet-shaped hexagonal boron nitride particles. The hexagonal boron nitride particles may also consist of aggregates of primary particles of hexagonal boron nitride, the primary particles comprising platelet-shaped hexagonal boron nitride particles. The aggregates of primary particles of hexagonal boron nitride may also be referred to as "boron nitride aggregates." The average particle size (d 50 The average particle size (d 50The average particle size (d 50 The average particle size (d ) of the primary particles of hexagonal boron nitride may be 20 to 500 μm, or 20 to 400 μm, or 30 to 500 μm, or 30 to 300 μm, or 50 to 400 μm, or 30 to 50 μm, or 50 to 100 μm, or 100 to 150 μm, or 100 to 200 μm, or 200 to 400 μm. 50 The average particle size (d ) of the boron nitride aggregates and the aggregates of primary particles may be 3 to 50 μm, or 3 to 30 μm, or 5 to 30 μm, or 8 to 30 μm, or 8 to 15 μm, or 10 to 15 μm, or 10 to 12 μm. 50 ) can be measured by laser diffraction. The boron nitride aggregates may have any shape, for example, spherical, irregular, or flake-shaped. Flake-shaped aggregates may have an aspect ratio of 1 to 20.

[0048] In some embodiments, the hexagonal boron nitride particles may comprise or consist of agglomerates of primary particles of hexagonal boron nitride, the primary particles comprising platelet-shaped hexagonal boron nitride particles, and the average particle size of the agglomerates (d 50 ) is 30 to 300 μm, and the average particle size of the primary particles of hexagonal boron nitride (d 50 ) is 8 to 15 μm.

[0049] In some embodiments, when the boron nitride aggregates are used as hexagonal boron nitride particles, the aggregates may be partially or completely broken down into primary particles in the final product, i.e., sheet. In some embodiments, when the boron nitride aggregates are used as hexagonal boron nitride particles, such as flake-shaped boron nitride aggregates, some or all of the aggregates may still be present in the final product in agglomerate form, i.e., the aggregates may not be broken down into primary particles in the sheet.

[0050] The hexagonal boron nitride particles may also comprise non-agglomerated platelet-shaped hexagonal boron nitride particles. The hexagonal boron nitride particles may also consist of non-agglomerated platelet-shaped hexagonal boron nitride particles. The average particle size (d 50 The average particle size (d 50 ) may also be 10 to 100 μm, or 10 to 50 μm, or 30 to 70 μm, or 30 to 60 μm, or 40 to 50 μm.

[0051] In some embodiments, a mixture of agglomerated and non-agglomerated platelet-shaped hexagonal boron nitride particles may be used.

[0052] Composite materials and sheets may have a porosity of up to 40%, or up to 30%, or up to 20%. Composite materials and sheets may have a porosity of at least 1%, or at least 2%, or at least 3%, or at least 4%, or at least 5%, or at least 8%, or at least 10%. In some embodiments, composite materials and sheets have a porosity of 0.5-40%, or 0.5-30%, or 0.5-20%, or 1-40%, or 1-30%, or 1-20%, or 2-40%, or 2-30%, or 2-20%, or 5-40%, or 5-30%, or 5-20%. In some embodiments, composite materials and sheets have a porosity of 0%.

[0053] The composite materials and sheets may have a density of at least 60%, or at least 70%, or at least 80%, or even at least 90% of theoretical density. The composite materials and sheets may have a density of up to 100%, or up to 99.5%, or up to 99%, or up to 98%, or up to 97%, or up to 96%, or up to 95%, or up to 92%, or up to 90% of theoretical density. The composite materials and sheets may have a density of 60-95%, 70-95%, 80-95%, 60-98%, 70-98%, 80-98%, 60-99%, 70-99%, 80-99%, 60-99.5%, 70-99.5%, 80-99.5%, 60-100%, 70-100%, or 80-100% of the theoretical density. Theoretical density can be calculated from the known densities of the components of the composite materials and sheets and from the weight fractions of the components.

[0054] The composite materials and sheets included in the sheet disclosed herein have good dielectric properties. Typically, the composite materials and sheets have a dielectric loss tangent (Df) of up to 0.009 at 5.2 GHz, and may be between 0.0001 and 0.009 at 5.2 GHz. The dielectric constant or relative permittivity (Dk) of the composite materials and sheets is typically up to 5.0 at 5.2 GHz, and may be between 2.0 and 4.0 at 5.2 GHz.

[0055] The presence of pores in the composite materials and sheets can improve the dielectric properties of the composite materials and sheets. Additionally, the presence of pores in the composite materials and sheets allows the composite materials and sheets to be compressible, which may be desirable for some applications. The pores in the composite materials and sheets should be small in size and uniformly distributed throughout the composite materials and sheets.

[0056] In some embodiments of the sheets disclosed herein, the composite material included in the sheet does not include fibers such as carbon fiber, glass fiber, or fibers made from other materials.

[0057] The sheets disclosed herein may have a Shore D hardness of up to 150. The Shore D hardness of the sheets may be from 20 to 150, or from 30 to 150, or from 30 to 100. The sheets may also have lower or higher hardnesses.

[0058] The thickness of the sheet disclosed herein may be 0.01 mm to 6 mm, or 0.05 mm to 6 mm, or 0.1 to 3 mm, or 0.5 to 2 mm. The size of the hexagonal boron nitride particles may be selected depending on the film thickness.

[0059] The width and length of the sheet may be up to several inches (e.g., 1 inch, 5 inches, 10 inches, 50 inches) or more. Typically, the sheet has a constant thickness across the width and length of the sheet. The sheet may also have a variable thickness, i.e., the thickness of the sheet is not constant across the width and length of the sheet.

[0060] The composite may further include additional thermally conductive fillers such as alumina, or other fillers.

[0061] In some embodiments of the sheet disclosed herein, the composite material may further include an organic liquid. The amount of organic liquid included in the composite material may be 0.1 to 10 weight percent, based on the total weight of the composite material. Useful organic liquids that can be included in the composite material are non-volatile organic liquids that have sufficient surface energy to wet the pores or remain trapped within the pores. The organic liquid that can be included in the composite material may be, for example, at least one of mineral oil, paraffin oil / wax, orange oil, vegetable oil, castor oil, or palm kernel oil. The organic liquid included in the composite material can reduce the hardness of the composite material and sheet, making it softer.

[0062] Small amounts of other additives can be added to the composite to provide additional functionality or to act as processing aids. These include viscosity modifiers (e.g., fumed silica, block copolymers, and waxes), plasticizers, heat stabilizers (e.g., those available from BASF, Ludwigshafen, Germany, under the trade name "Irganox 1010"), antimicrobial agents (e.g., silver and quaternary ammonium), flame retardants, antioxidants, dyes, pigments, and ultraviolet (UV) stabilizers. Also, low particle size (e.g., average particle size (d) of less than 1 μm) is preferred. 50 Thermally conductive particles such as carbon or hexagonal boron nitride having )) may be used as viscosity modifiers.

[0063] If necessary, an elastomer can be added to the composite to improve its elasticity, i.e., reduce its brittleness. Any elastomer that can be mixed or blended with a polymer and hexagonal boron nitride particles may be used. Suitable elastomers include, for example, Santoprene 8211-35 available from Celanese (Irving, TX, US), Kraton 1645 available from Kraton (Houston, TX, US), Vector Thermoplastic Elastomers 2518 available from TSRC Corporation (Taiwan), Kraton D11671 PT available from Kraton (Houston, TX, US), and Pebax 4033 available from Arkema (Colombes, France).

[0064] In some embodiments of the sheets disclosed herein, the composite material comprises at least 70, or at least 80, or at least 85, or at least 90, or more than 90, or at least 91, or at least 92 weight percent hexagonal boron nitride particles, based on the total weight of the composite material, and the composite material has a porosity of at least 2%, preferably 2-30%.

[0065] In some embodiments of the sheet disclosed herein, the composite comprises at least 70, or at least 80, or at least 85, or at least 90, or more than 90, or at least 91, or at least 92 weight percent hexagonal boron nitride particles, based on the total weight of the composite, and the sheet has a through thickness thermal conductivity of at least 15 W / m×K, or at least 20 W / m×K.

[0066] In some embodiments of the sheets disclosed herein, the composite comprises at least 70, or at least 80, or at least 85, or at least 90, or more than 90, or at least 91, or at least 92 weight percent hexagonal boron nitride particles, based on the total weight of the composite, and the sheet has an orientation index of at least 6, or at least 8, or at least 10.

[0067] In some embodiments of the sheet disclosed herein, the composite comprises at least 70, or at least 80, or at least 85, or at least 90, or more than 90, or at least 91, or at least 92 weight percent hexagonal boron nitride particles, based on the total weight of the composite; the composite has a porosity of at least 2%, preferably 2-30%; the sheet has a through-thickness thermal conductivity of at least 15 W / m×K, or at least 20 W / m×K; and the sheet has an orientation index of at least 6, or at least 8, or at least 10.

[0068] In some embodiments of the sheets disclosed herein, the hexagonal boron nitride particles have an average particle size (d 50 The present invention comprises or consists of non-agglomerated platelet-shaped hexagonal boron nitride particles having a crystalline structure.

[0069] In some embodiments of the sheets disclosed herein, the hexagonal boron nitride particles comprise aggregates of primary particles of hexagonal boron nitride, the primary particles comprising platelet-shaped hexagonal boron nitride particles, and the average particle size of the aggregates (d 50) is 30 to 500 μm, and the average particle size of the primary particles of hexagonal boron nitride (d 50 ) is 3 to 50 μm.

[0070] Typically, the composite material of the sheet and the sheet disclosed herein does not contain silicone.

[0071] The composite materials of the sheets disclosed herein are obtained by densifying a material comprising a porous network of polymers.

[0072] First Method A first method for producing the sheet disclosed herein comprises: providing hexagonal boron nitride particles comprising a polymer, a solvent, and platelet-shaped hexagonal boron nitride particles; combining a polymer, a solvent, and hexagonal boron nitride particles to form a suspension of hexagonal boron nitride particles in a polymer solvent solution, wherein the polymer in the polymer solvent solution has a melting point and the solvent has a boiling point, and the step of combining the polymer, the solvent, and the hexagonal boron nitride particles is performed at a temperature above the melting point of the polymer in the polymer solvent solution and below the boiling point of the solvent; forming the suspension into a film, the platelet-shaped hexagonal boron nitride particles being oriented in a direction parallel to the plane of the film; inducing phase separation of the polymer from the solvent; removing at least a portion of the solvent from the film to obtain a porous film; Optionally, compressing the porous film to obtain a densified film; laminating multiple films, either porous or densified, one after the other to obtain a film laminate; pressing the film laminate to obtain a bonded film laminate; and slicing a sheet from the bonded film stack in a direction perpendicular to the plane of the laminated film layers.

[0073] To produce the sheets disclosed herein by the first method, the polymers and hexagonal boron nitride particles described in more detail above can be used.

[0074] The solvent is typically selected so that it can dissolve the polymer and form a polymer-solvent solution, i.e., the solvent must be miscible with the polymer. Dissolution of the polymer can be facilitated by heating the solution to an elevated temperature. In some embodiments, combining the polymer and solvent is carried out at a temperature ranging from 20°C to 350°C. Hexagonal boron nitride particles may be added to any or all of the combining steps, before the polymer dissolves, after the polymer dissolves, or at any time in between.

[0075] The solvent is selected to form a polymer-solvent solution. The solvent may be a blend of at least two individual solvents. In some embodiments, when the polymer is a polyolefin (e.g., at least one of polyethylene and polypropylene), the solvent may be, for example, at least one of mineral oil, tetralin, decalin, orthodichlorobenzene, cyclohexane-toluene mixture, dodecane, paraffin oil / wax, kerosene, isoparaffin fluid, p-xylene / cyclohexane mixture (1 / 1 wt / wt), camphene, 1,2,4 trichlorobenzene, octane, orange oil, vegetable oil, castor oil, or palm kernel oil. In some embodiments, when the polymer is polyvinylidene fluoride, the solvent may be, for example, at least one of ethylene carbonate, propylene carbonate, or 1,2,3 tricetoxypropane.

[0076] The polymer, solvent, and hexagonal boron nitride particles may be combined using conventional mixing aggregates such as industrial mixers, including, but not limited to, a twin screw extruder, a planetary extruder, a conical twin screw extruder, a kneader, or a double planetary mixer.

[0077] In some embodiments of the first method, the polymer in the polymer solvent solution has a melting point, the solvent has a boiling point, and the step of combining the polymer, the solvent, and the hexagonal boron nitride particles may be performed at a temperature above the melting point of the polymer in the polymer solvent solution and below the boiling point of the solvent. Combining the polymer, the solvent, and the hexagonal boron nitride particles forms a suspension of hexagonal boron nitride particles in the polymer solvent solution.

[0078] After forming a suspension of hexagonal boron nitride particles in a polymer solvent solution, the suspension is formed into a film. In the film, the platelet-shaped hexagonal boron nitride particles are oriented in a direction parallel to the plane of the film. The film may be a continuously formed film, or a film or layer containing a microreplicated or macroreplicated structure and made by microreplicated or microreplicated techniques. Film formation can be carried out using techniques known in the art, including knife coating, roll coating (e.g., roll coating through a defined nip), and extrusion (e.g., extrusion through a die (e.g., extrusion through a die having appropriate layer dimensions (i.e., die gap width and thickness))).

[0079] In one exemplary embodiment, the polymer solvent solution has a paste-like consistency and is formed into a film by extrusion (eg, through a die having appropriate layer dimensions (ie, die gap width and thickness)).

[0080] After forming the suspension into a film, if the polymer is miscible in the solvent, the polymer is then induced to phase separate. Several techniques can be used to induce phase separation, including at least one of thermally induced phase separation or solvent-induced phase separation. Thermally induced phase separation can occur when the temperature at which induced phase separation occurs is lower than the temperature at which the polymer, solvent, and hexagonal boron nitride particles are combined. This can be achieved by cooling the polymer-solvent solution if the combining step is performed near room temperature, or by first heating the polymer-solvent solution to a high temperature (either during or after the combining step) and then lowering the temperature of the polymer-solvent solution, thereby inducing phase separation of the polymer. In either case, cooling can result in phase separation of the polymer from the solvent. Solvent-induced phase separation can be carried out by adding a second solvent, i.e., a poor solvent for the polymer, to the polymer-solvent solution, or can be achieved by removing at least a portion of the solvent from the polymer-solvent solution (e.g., by evaporating at least a portion of the solvent from the polymer-solvent solution), thereby inducing phase separation of the polymer. A combination of phase separation techniques (e.g., thermally induced and solvent-induced phase separation) can also be utilized. Thermally induced phase separation can be advantageous if the combining step is performed at an elevated temperature, as this also promotes polymer dissolution. In some embodiments, thermally induced phase separation is performed at a lower temperature than the combining temperature, in the range of 5 to 300°C (in some embodiments, in the range of 5 to 250, 5 to 200, 5 to 150, 15 to 300, 15 to 250, 15 to 200, 15 to 130, or even 25 to 110°C).

[0081] In some embodiments of the first method, the polymer in the polymer solvent solution has a melting point, and the step of inducing phase separation is carried out at a temperature below the melting point of the polymer in the polymer solvent solution.

[0082] During induced phase separation, a polymer network structure can be formed. In some embodiments, phase separation is induced thermally (e.g., by thermally induced phase separation (TIPS) by quenching to a low temperature), chemically (e.g., by solvent-induced phase separation (SIPS) by replacing a good solvent with a poor solvent), or by changing the solvent ratio (e.g., by evaporating one of the solvents). Other phase separation or pore formation techniques known in the art, such as discontinuous polymer blending (sometimes referred to as polymer-assisted phase inversion (PAPI)), moisture-induced phase separation, or vapor-induced phase separation, can also be used. The polymer network structure can be inherently porous (i.e., have pores). The pore structure can be open, allowing fluid communication from the interior region of the polymer network structure to the outer surface of the polymer network structure and / or between a first surface of the polymer network structure and a second surface of the polymer network structure opposite the first surface.

[0083] The polymer network structure may be described as a porous polymer network or a porous phase-separated polymer network. Generally, the porous polymer network (as manufactured) comprises an interconnected porous polymer network structure comprising a plurality of interconnected morphologies (e.g., at least one of fibrils, nodules, nodes, open cells, closed cells, lobed lace, strands, spheres, or honeycombs). The interconnected polymer structure may adhere directly to the surface of the hexagonal boron nitride particles and act as a binder for the hexagonal boron nitride particles. In this regard, the spaces between adjacent hexagonal boron nitride particles (e.g., primary particles or aggregates) may comprise a porous polymer network structure, as opposed to a solid matrix material.

[0084] In some embodiments, the polymer network structure may comprise a three-dimensional network comprising an interconnected network of polymer fibrils, in some embodiments, the individual fibrils have an average width in the range of 10 nm to 100 nm (in some embodiments, 100 nm to 500 nm, or even 500 nm to 5 micrometers).

[0085] In some embodiments, the hexagonal boron nitride particles are dispersed within the polymer network structure, such that the outer surfaces of individual units of hexagonal boron nitride particles (e.g., individual particles or individual agglomerates) are largely free of contact or coating by the polymer network structure. In this regard, in some embodiments, the average percentage area coverage of the polymer network structure with respect to the outer surfaces of the individual particles (i.e., the percentage of the outer surface area that is in direct contact with the polymer network structure) is 50 percent or less (in some embodiments, 40, 30, 25, 20, 10, 5, or even 1 percent or less), based on the total surface area of ​​the outer surfaces of the individual particles. Without being bound by theory, it is believed that the large, non-contacting surface area coating on the hexagonal boron nitride particles allows for increased particle-to-particle contact during compression, which in turn increases thermal conductivity.

[0086] After the phase separation inducing step causes the polymer to phase separate from the solvent, at least a portion of the solvent may be removed from the film, i.e., from the polymer network structure of the film, thereby forming a porous film having a polymer network structure with hexagonal boron nitride particles distributed within the polymer network structure.

[0087] The solvent (e.g., the first solvent) can be removed by evaporation; solvents with high vapor pressures are particularly suited to this removal method. However, if the first solvent has a low vapor pressure, it may be desirable to extract the first solvent with a second solvent with a higher vapor pressure, followed by evaporation of the second solvent. In some embodiments, in the range of 10 to 100 weight percent (in some embodiments, in the range of 20 to 100, 30 to 100, 40 to 100, 50 to 100, 60 to 100, 70 to 100, 80 to 100, 90 to 100, 95 to 100, or even 98 to 100 weight percent) of the solvent, and second solvent, if used, can be removed from the film.

[0088] For example, in some embodiments, when mineral oil is used as the first solvent, hot (e.g., about 60°C) isopropanol or a blend of methyl nonafluorobutyl ether (C4F9OCH3), ethyl nonafluorobutyl ether (C4F9OC2H5), and trans-1,2-dichloroethylene (e.g., available from 3M Company, St. Paul, MN, under the trade designation "NOVEC 72DE") can be used as the second solvent to extract the first solvent, followed by evaporation of the second solvent. In some embodiments, when at least one of vegetable oil or palm kernel oil is used as the first solvent, hot (e.g., about 60°C) isopropanol can be used as the second solvent. In some embodiments, when ethylene carbonate is used as the first solvent, water can be used as the second solvent.

[0089] In some embodiments of the first method, the phase-separated film formed has a porosity of at least 5 percent (in some embodiments, at least 10, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or even at least 80 percent, in some embodiments, in the range of 25 to 80 percent) after removal of the solvent. This porosity results from phase separation of the polymer from the solvent, which fills the pores in the polymer network, leaving no initially unfilled voids. After the solvent is completely or partially removed, pores form in the polymer network.

[0090] Typically, the polymer used in the first method disclosed herein is a thermoplastic polymer.

[0091] The thickness of the porous and densified films may be, for example, 5 to 150 mils (0.127 to 3.81 mm). The thickness of the porous and densified films may also be less than 5 mils or greater than 150 mils.

[0092] Second Method A second method for producing the sheets disclosed herein comprises: providing hexagonal boron nitride particles comprising a polymer, a solvent, and platelet-shaped hexagonal boron nitride particles; combining (e.g., mixing or blending) a polymer, a solvent, and hexagonal boron nitride particles to form a slurry, wherein the slurry is a suspension of polymer and hexagonal boron nitride particles in a solvent, the polymer having a melting point and the solvent having a boiling point, and wherein combining the polymer, solvent, and hexagonal boron nitride particles is performed at a temperature below the melting point of the polymer and below the boiling point of the solvent; forming the slurry into a film, wherein the platelet-shaped hexagonal boron nitride particles are oriented in a direction parallel to the plane of the film; heating the film in an environment that maintains at least 90 (in some embodiments, at least 91, 92, 93, 94, 95, 96, 97, 98, 99, 99.5, or even 100) weight percent of the solvent in the film, based on the weight of the solvent in the film, to solubilize at least 50 (in some embodiments, at least 55, 60, 65, 70, 75, 80, 85, 90, 95, 96, 97, 98, 99, or even 100) weight percent of the polymer in the solvent, based on the total weight of the polymer; Inducing phase separation of the polymer from the solvent; removing at least a portion of the solvent from the film (in some embodiments, at least 50, 55, 60, 65, 70, 75, 80, 95, 96, 97, 98, 99, 99.5, or even 100 weight percent of the solvent, based on the weight of the solvent in the film) to obtain a porous film; Optionally, compressing the porous film to obtain a densified film; laminating multiple films, either porous or densified, one after the other to obtain a film laminate; pressing the film laminate to obtain a bonded film laminate; and slicing a sheet from the bonded film stack in a direction perpendicular to the plane of the laminated film layers.

[0093] Typically, the polymer used in the second method disclosed herein is a thermoplastic polymer.

[0094] To produce the sheets disclosed herein by the second method, the polymers and hexagonal boron nitride particles described in more detail above can be used.

[0095] The solvent is typically selected so that it can dissolve the polymer and form a polymer-solvent solution, i.e., the solvent must be miscible with the polymer. Dissolution of the polymer can be facilitated by heating the solution to an elevated temperature. In some embodiments, combining the polymer and solvent is carried out at a temperature ranging from 20°C to 350°C. Hexagonal boron nitride particles may be added to any or all of the combining steps, before the polymer dissolves, after the polymer dissolves, or at any time in between.

[0096] In some embodiments of the second method, the solvent is a blend of at least two individual solvents. In some embodiments, when the polymer is a polyolefin (e.g., at least one of polyethylene or polypropylene), the solvent can be at least one of mineral oil, tetralin, decalin, orthodichlorobenzene, a cyclohexane-toluene mixture, dodecane, paraffin oil / wax, kerosene, a p-xylene / cyclohexane mixture (1 / 1 wt / wt), camphene, 1,2,4 trichlorobenzene, octane, orange oil, vegetable oil, castor oil, or palm kernel oil. In some embodiments, when the polymer is polyvinylidene fluoride, the solvent is at least one of ethylene carbonate, propylene carbonate, or 1,2,3 triacetoxypropane.

[0097] The slurry can be continuously mixed or blended to prevent or reduce settling or separation of the polymer and / or particles from the solvent. Typically, continuous mixing or blending is not necessary to prevent or reduce settling or separation of the polymer and / or particles from the solvent. In some embodiments, the slurry is degassed using techniques known in the art to remove trapped air.

[0098] The slurry resulting from the step of combining (eg, mixing or blending) the polymer, solvent, and hexagonal boron nitride particles is a suspension of the polymer and hexagonal boron nitride particles in the solvent.

[0099] The polymer, solvent, and hexagonal boron nitride particles may be combined using conventional mixing aggregates such as industrial mixers, including but not limited to, twin screw extruders, planetary extruders, conical twin screw extruders, kneaders, or double planetary mixers.

[0100] In some embodiments of the second method, the weight ratio of solvent to polymer is at least 9:1.

[0101] In some embodiments of the second method, the combining step is carried out at a temperature below the melting point of the polymer and below the boiling point of the solvent.

[0102] The polymer provided for the method disclosed herein has a melting point, and the solvent has a boiling point. In some embodiments of the second method, the step of combining the polymer, the solvent, and the hexagonal boron nitride particles is carried out at a temperature lower than the melting point of the polymer and lower than the boiling point of the solvent. The step of combining the polymer, the solvent, and the hexagonal boron nitride particles forms a slurry, i.e., a suspension of the polymer and the hexagonal boron nitride particles in the solvent.

[0103] The slurry can be formed into a film using techniques known in the art, including knife coating, roll coating (e.g., roll coating through a defined nip), and coating through any number of different dies having appropriate dimensions or profiles. These coating techniques can be performed between two liners.

[0104] In some embodiments, it may be desirable to form the film at room temperature for ease of manufacturing.

[0105] In some embodiments of the second method, the step of heating the film is carried out at a temperature above the melting point of the miscible polymer-solvent solution and below the boiling point of the solvent.

[0106] In some embodiments of the second method, the step of inducing phase separation is carried out at a temperature below the melting point of the polymer in the slurry. Without wishing to be bound, it is believed that in some embodiments, the solvent used to prepare the miscible blend with the polymer may cause a melting point depression in the polymer. The melting points described herein include those below any melting point depression of the polymer-solvent system.

[0107] The step of inducing phase separation is carried out below the melting point of the polymer.

[0108] During induced phase separation, a polymer network structure can be formed. In some embodiments, phase separation is thermally induced (e.g., by thermally induced phase separation (TIPS) by rapidly cooling to a temperature lower than that used during heating). Cooling can be achieved, for example, in air, in a liquid, or at a solid interface, and can be varied to control phase separation. The polymer network structure can be inherently porous (i.e., have pores). The pore structure can be open, allowing fluid communication from the interior region of the polymer network structure to the outer surface of the polymer network structure and / or between a first surface of the polymer network structure and a second surface of the polymer network structure opposite the first surface.

[0109] The polymer network structure may be described as a porous polymer network or a porous phase-separated polymer network. Generally, the porous polymer network (as manufactured) comprises an interconnected porous polymer network structure comprising a plurality of interconnected morphologies (e.g., at least one of fibrils, nodules, nodes, open cells, closed cells, lobed lace, strands, spheres, or honeycombs). The interconnected polymer structure may adhere directly to the surface of the hexagonal boron nitride particles and act as a binder for the hexagonal boron nitride particles. In this regard, the space between adjacent hexagonal boron nitride particles (e.g., primary particles or aggregates) may comprise a porous polymer network structure, as opposed to a solid matrix material.

[0110] The polymer network structure may include multiple nodes interconnected by multiple fibrils. Typically, the nodes have a diameter of 1 to 50 μm. The diameter is measured as the maximum diameter in a scanning electron micrograph of the composite. The fibrils connecting the individual nodes may have a diameter of 80 to 2000 nm and a length of 1 to 50 μm.

[0111] The nodes and fibrils comprise a polymer. The nodes and fibrils may consist of a polymer. The hexagonal boron nitride particles may be located near or within the nodes. The hexagonal boron nitride particles may also be located near or connected to the fibrils. The fibrils may be mechanically fixed to the hexagonal boron nitride particles, or in other words, the hexagonal boron nitride particles may act as nodes to which the fibrils are mechanically fixed. The porosity of the composite material results from pores located between the fibrils.

[0112] The fibrils of the composite material contained in the sheet disclosed herein differ from fibers known in the art. Fibers are a possible macroscopic shape of a material, typically having a length of at least 100 μm, e.g., at least 1 mm and up to 30 mm, and multiple fibers may be included in a heterogeneous woven or braided structure. In contrast, the fibrils of the composite material contained in the sheet disclosed herein are microscopic structures having a typical diameter of 80 to 2000 nm (e.g., 80 to 800 nm) and a length of 1 to 50 μm, each of which is interconnected with a node.

[0113] In some embodiments, the polymer network structure may comprise a three-dimensional network comprising an interconnected network of polymer fibrils, in some embodiments, the individual fibrils have an average width in the range of 10 nm to 100 nm (in some embodiments, 100 nm to 500 nm, or even 500 nm to 5 micrometers).

[0114] In some embodiments, the hexagonal boron nitride particles are dispersed within the polymer network structure, such that the outer surfaces of individual units of hexagonal boron nitride particles (e.g., individual particles or individual agglomerates) are largely free of contact or coating by the polymer network structure. In this regard, in some embodiments, the average percentage area coverage of the polymer network structure with respect to the outer surfaces of the individual particles (i.e., the percentage of the outer surface area that is in direct contact with the polymer network structure) is 50 percent or less (in some embodiments, 40, 30, 25, 20, 10, 5, or even 1 percent or less), based on the total surface area of ​​the outer surfaces of the individual particles. Without wishing to be bound by theory, it is believed that the large, non-contacting surface area coating on the hexagonal boron nitride particles allows for increased particle-to-particle contact during compression, thus increasing thermal conductivity.

[0115] After phase separation, at least a portion of the solvent is removed from the film. Removing at least a portion of the solvent from the film results in a porous film. In some embodiments of the second method, at least 90 weight percent of the solvent is removed, based on the weight of the solvent in the film. Before removing at least 90 weight percent of the solvent, based on the weight of the solvent in the film, the film has a first volume, and after removing at least 90 weight percent of the solvent, based on the weight of the solvent in the film, the film has a second volume, and the difference between the first volume and the second volume (i.e., (first volume minus second volume) divided by the first volume and multiplied by 100) is less than 10 percent (in some embodiments, less than 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.75, 0.5 percent, or even less than 0.3 percent). Volatile solvent can be removed from the film, for example, by evaporating the solvent from at least one major surface of the film. Evaporation can be assisted, for example, by applying at least one of heat, vacuum, or airflow. Evaporation of flammable solvents can be achieved in a solvent-rated oven. However, if a solvent (e.g., a first solvent) has a low vapor pressure, a second solvent with a higher vapor pressure can be used to extract the first solvent, followed by evaporation of the second solvent. For example, in some embodiments, when mineral oil is used as the first solvent, hot (e.g., about 60°C) isopropanol or a blend of methyl nonafluorobutyl ether (C4F9OCH3), ethyl nonafluorobutyl ether (C4F9OC2H5), and trans-1,2-dichloroethylene (e.g., available under the trade name "NOVEC 72E" from 3M Company, St. Paul, MN) can be used as the second solvent to extract the first solvent, followed by evaporation of the second solvent. In some embodiments, when at least one of vegetable oil or palm kernel oil is used as the first solvent, hot (e.g., about 60°C) isopropanol can be used as the second solvent.In some embodiments, when ethylene carbonate is used as the first solvent, water can be used as the second solvent.

[0116] In some embodiments of the second method, the film has first and second major surfaces, with edges perpendicular to the first and second major surfaces, and the edges are unrestrained during solvent removal. This can be done, for example, by drying a portion of the layer without restraint in an oven. Continuous drying can be achieved, for example, by drying a length of the layer supported on a belt as it is conveyed through an oven. Alternatively, to facilitate removal of the non-volatile solvent, the solvent can be exchanged, for example, by conveying a length of the film continuously through a bath of a compatible volatile solvent, followed by drying the film without restraint. However, it is not necessary to remove all of the non-volatile solvent from the film during solvent exchange. A small amount of non-volatile solvent may remain and act as a plasticizer for the polymer.

[0117] In some embodiments of the second method, the phase-separated film formed has a porosity of at least 5 percent (in some embodiments, at least 10, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or even at least 80 percent, in some embodiments, in the range of 25 to 80 percent) after removal of the solvent. This porosity results from phase separation of the polymer from the solvent, which fills the pores in the polymer network, leaving no initially unfilled voids. After the solvent is completely or partially removed, pores form in the polymer network.

[0118] In some embodiments of the first and second methods, up to 10 weight percent of a non-volatile solvent or organic liquid remains in the porous film after solvent removal, improving the elasticity of the porous film and sheets made from the porous film. Up to 10 weight percent of a non-volatile organic liquid can also be added after solvent removal.

[0119] The first and second methods optionally include compressing the porous film after removing at least a portion of the solvent from the film. Compressing the porous film densifies the porous film. Compressing the polymer film can be accomplished, for example, by a conventional calendering process known in the art.

[0120] Compressing the porous film plastically deforms the polymer network structure of the porous film. Vibrational energy may be applied during the application of the compression force. In some embodiments, the porous film is in the form of a strip of indefinite length, and the compression force is applied as the strip passes through a nip. A tensile load may be applied as the strip passes through the nip. For example, the nip may be formed between two rollers, at least one of which applies vibrational energy, between a roller and a bar, at least one of which applies vibrational energy, or between two bars, at least one of which applies vibrational energy. The application of compression and vibrational energy may be achieved in a continuous roll-to-roll manner or a step-and-repeat manner. In other embodiments, the compression force is applied to individual layers, for example, between a platen and a platen, at least one of which applies vibrational energy. In some embodiments, the vibrational energy is in the ultrasonic range (e.g., 20 kHz), although other ranges may be suitable.

[0121] The density of the densified film may be at least 60% (in some embodiments at least 70%, at least 80%, at least 90%, or even 100%, and in some embodiments in the range of 60-98%, 70-98%, 80-98%, 60-100%, 70-100%, or even 80-100%) of the theoretical density after densification. The theoretical density can be calculated from the known densities of the components of the densified porous film and from the weight fractions of the components.

[0122] By compressing the porous film, the density and thermal conductivity of the film increase by increasing particle-to-particle contact of the hexagonal boron nitride particles. Compressing the porous film increases density, which reduces the insulating air volume (or porosity) of the film, thus increasing thermal conductivity. Similarly, increasing particle-to-particle contact of the hexagonal boron nitride particles can be measured by an increase in thermal conductivity.

[0123] Compression of the porous polymer network structure of the film results in a film with a higher density and a compressed polymer network structure, with the hexagonal boron nitride particles distributed within the polymer network and increased particle-to-particle contact.

[0124] If the porous film is not compressed prior to lamination of multiple layers, the density and thermal conductivity are increased by pressing the film stack, which compresses the porous polymer network structure of the film. The step of pressing the film stack increases particle-to-particle contact of the hexagonal boron nitride particles.

[0125] The through-thickness thermal conductivity of the uncompressed porous film may be in the range of 0.2 to 0.8 W / m×K, and the in-plane thermal conductivity of the uncompressed porous film may be in the range of 0.80 to 2.0 W / m×K. The through-thickness thermal conductivity of the compressed densified film may be in the range of 0.80 to 3.5 W / m×K, and the in-plane thermal conductivity of the compressed densified film may be in the range of 4.0 to 45 W / m×K.

[0126] The sheet manufacturing methods disclosed herein, i.e., the first and second methods, include the step of laminating multiple layers of either porous films or densified films one after the other. If the porous films are not densified before lamination, multiple layers of porous films are laminated one after the other. If the porous films are densified before lamination, multiple layers of densified films are laminated one after the other. By laminating multiple layers of either porous films or densified films, a film laminate is obtained.

[0127] To laminate multiple layers of porous or densified films, the porous or densified films may be cut into pieces of equal size, and the pieces may be laminated together.

[0128] The step of pressing the film stack in the first and second methods is carried out at a pressure, temperature, and time sufficient to ensure bonding of the individual film layers to the bonded film stack, i.e., the bonding block.

[0129] The step of pressing the film laminate in the first and second methods may be carried out at a temperature of at least 110°F (43°C), and typically at a temperature of up to 575°F (302°C). For example, if the polymer used to make the sheet composites disclosed herein is ultra-high molecular weight polyethylene, the step of pressing the film laminate may be carried out at a temperature of at least 275°F (135°C), and typically at a temperature of up to 400°F (204°C). This pressing step results in a bonded film laminate.

[0130] It has been found that a minimum pressing pressure is necessary to press the film laminate.

[0131] Advantageously, the step of pressing the film stack may be carried out under a pressing pressure of at least 2.0 MPa. Using a pressing pressure of at least 2.0 MPa ensures that the individual layers of the film stack are bonded to one another, resulting in a bonded film stack, i.e., a bonded block, in which the individual film layers are seamlessly bonded to one another.

[0132] It has been further discovered that by further increasing the pressing pressure above the minimum pressing pressure of 2.0 MPa, the through-thickness thermal conductivity of the resulting sheet after the subsequent slicing step can be further significantly increased. Without being bound by theory, it is believed that this can be explained by increased layer-to-layer, i.e., particle-to-particle contact of the hexagonal boron nitride particles between the original individual adjacent film layers in the bonded film stack formed during pressing.

[0133] Typically, the step of pressing the film laminate is carried out under a pressing pressure of up to 40 MPa. Higher pressing pressures are possible, but are not typically necessary, as increasing the pressing pressure beyond 40 MPa typically does not further increase the through-thickness thermal conductivity of the sheet.

[0134] Typically, the step of pressing the film stack is carried out for at least 2 minutes.

[0135] Advantageously, the step of pressing the film stack may be carried out in a press direction (i.e., z-direction) while the film stack is constrained in first and second directions (i.e., x-direction and y-direction) perpendicular to the press direction, the first direction being perpendicular to the second direction. For example, a mold, for example a steel mold, can be used to constrain the stack in the x-direction and y-direction. Another possibility is to press the film stack in the press direction (i.e., z-direction), while constraining the film stack in a first direction (i.e., x-direction) perpendicular to the press direction and stretching the film stack in a second direction (i.e., y-direction) perpendicular to the press direction, the first direction being perpendicular to the second direction.

[0136] The x-direction, or first direction perpendicular to the pressing direction, is a first direction parallel to the plane of the layers of the porous or densified film. The y-direction, or second direction perpendicular to the pressing direction, is a second direction parallel to the plane of the layers of the porous or densified film. The z-direction, or pressing direction, is a direction perpendicular to the plane of the layers of the porous or densified film.

[0137] The methods disclosed herein for producing the sheet of the present disclosure, namely the first and second methods, include: The method may further include the step of heating the film laminate before pressing the film laminate.

[0138] Advantageously, the film laminate may be heated to a temperature of 110°F to 575°F (43°C to 302°C) before pressing the film laminate. The temperature selected is typically near or above the melting temperature of the polymer binder. For example, if the polymer used to make the sheet composites disclosed herein is ultra-high molecular weight polyethylene, the film laminate may be heated to a temperature of 275°F to 400°F (135°C to 204°C) before pressing the film laminate.

[0139] By heating the film stack before pressing it, better bonding between the individual laminated film layers can be obtained.

[0140] The first and second methods involve slicing sheets from the bonded film stack in a direction perpendicular to the plane of the laminated film layers.

[0141] The slicing (or cutting) step may be performed by using a skiving knife. A pneumatic cylinder may be used to force the bonded film laminate across the knife. The bonded film laminate may be heated to make cutting easier. A force may also be applied to hold the bonded film laminate down against the knife.

[0142] The sheets obtained by the first and second methods comprise a composite material comprising a polymer and platelet-shaped hexagonal boron nitride particles, the platelet-shaped hexagonal boron nitride particles being oriented in a direction perpendicular to the plane of the sheet. By orienting the platelet-shaped hexagonal boron nitride particles in a direction perpendicular to the plane of the sheet, and by virtue of the high loading of the hexagonal boron nitride particles in the composite, a sheet having a high through-thickness thermal conductivity can be obtained.

[0143] The methods disclosed herein for producing the sheet of the present disclosure, namely the first and second methods, include: The method may further include heating the bonded film stack prior to slicing the sheets from the bonded film stack.

[0144] Advantageously, the bonded film laminate may be heated to a temperature of 110°F to 575°F (43°C to 302°C) before slicing sheets from the bonded film laminate. The temperature selected is typically near or above the melting temperature of the polymer binder. For example, if the polymer used to make the sheet composites disclosed herein is ultra-high molecular weight polyethylene, the bonded film laminate may be heated to a temperature of 275°F to 400°F (135°C to 204°C) before slicing sheets from the bonded film laminate.

[0145] Prior to slicing the sheets from the bonded film laminate, the bonded film laminate is softened by heating the bonded film laminate, which makes slicing easier.

[0146] Figures 1a and 1b show scanning electron micrographs (SEM) of a cross section of a sheet disclosed herein. Figure 1b is a detail of Figure 1a at a larger magnification. In Figure 1b, platelet-shaped hexagonal boron nitride particles 1 are distributed in the sheet within a network of polymer material 2. The platelet-shaped hexagonal boron nitride particles 1 have an orientation perpendicular to the direction of the plane of the sheet. The direction perpendicular to the direction of the plane of the sheet is indicated by the white arrow in Figure 1a (thickness direction).

[0147] FIG. 2 shows a schematic representation of stacking multiple densified films one on top of the other to obtain a film stack, and slicing sheets from the bonded film stack in a direction perpendicular to the plane of the stacked film layers. In the first step of the method disclosed herein, a porous film 3 is formed, comprising platelet-shaped hexagonal boron nitride particles 1 oriented in a direction parallel to the plane of the film. In an optional method step, the porous film can be densified to obtain a densified film. The white arrows in FIG. 2 represent the direction perpendicular to the basal plane of the hexagonal boron nitride particles, while the black arrows in FIG. 2 represent the direction parallel to the basal plane of the hexagonal boron nitride particles. In the left-hand drawing of a single film layer 3 (porous or densified) in FIG. 2, the white arrow (representing the direction perpendicular to the basal plane of the hexagonal boron nitride particles, which is the direction of low thermal conductivity) is oriented perpendicular to the plane of the film, i.e., through the thickness of the film. The black arrows (representing the direction parallel to the basal plane of the hexagonal boron nitride particles, the direction of high thermal conductivity) are oriented parallel to the plane of the film, i.e., in the in-plane direction of the film. In a further step of the method disclosed herein, multiple porous or densified films 3 are stacked one on top of the other to obtain a film stack 4. In the drawing of film stack 4 in FIG. 2, the white arrows (representing the direction perpendicular to the basal plane of the hexagonal boron nitride particles, the direction of low thermal conductivity) are oriented perpendicular to the plane of the multiple layers of porous or densified film. In the next step of the method disclosed herein, the film stack 4 is pressed to obtain a bonded film stack 5. From the bonded film stack 5, a sheet 6 is sliced ​​in a direction perpendicular to the plane of the stacked film layers. In the drawing of sheet 7 on the right side of FIG. 2, the sheet 6 obtained by the slicing step is rotated 90 degrees so that the plane of the obtained sheet is now parallel to the plane of the drawing. In the drawing of sheet 7, the white arrows (representing the direction normal to the basal plane of the hexagonal boron nitride particles, the direction of low thermal conductivity) are oriented parallel to the direction of the plane of the sheet, i.e., in the plane of the sheet, and the black arrows (representing the direction parallel to the basal plane of the hexagonal boron nitride particles, the direction of high thermal conductivity) are oriented perpendicular to the direction of the plane of the sheet, i.e., through the thickness of the film.

[0148] The sheets disclosed herein are useful as thermal interface materials. Such thermal interface materials are useful for managing heat flow to or from different components, such as electronic devices (e.g., batteries, motors, refrigerators, circuit boards, solar cells, and heaters). In some embodiments, an article (e.g., an electronic device) comprises a heat source and a sheet described herein in contact with the heat source.

[0149] Illustrative Embodiments 1A. A sheet comprising a composite material comprising a polymer and hexagonal boron nitride particles, wherein the hexagonal boron nitride particles comprise platelet-shaped hexagonal boron nitride particles, the platelet-shaped hexagonal boron nitride particles being oriented in a direction perpendicular to the direction of the plane of the sheet, the composite material comprising at least 70 weight percent hexagonal boron nitride particles based on the total weight of the composite material, and the sheet having a through-thickness thermal conductivity greater than 12 W / m×K.

[0150] 2A. The sheet of Exemplary Embodiment 1A, wherein the composite material is obtained by densifying a material comprising a porous network of polymers.

[0151] 3A. The sheet of any one of the exemplary embodiments of A above, wherein the composite material comprises at least 80 weight percent, preferably at least 85 weight percent, more preferably at least 90 weight percent, and more preferably more than 90 weight percent hexagonal boron nitride particles, based on the total weight of the composite material.

[0152] 4A. The sheet of any one of the preceding exemplary embodiments of A, wherein the sheet has a through-thickness thermal conductivity of at least 15 W / m×K.

[0153] 5A. The sheet of any one of the preceding exemplary embodiments of A, wherein the composite material is electrically insulating.

[0154] 6A. A sheet according to any one of the preceding exemplary embodiments of A, wherein the orientation index of the sheet is greater than 4.0.

[0155] 7A. Average particle size (d 50 ) is 0.5 μm to 500 μm.

[0156] 8A. Hexagonal boron nitride particles comprise aggregates of primary particles of hexagonal boron nitride, the primary particles comprise platelet-shaped hexagonal boron nitride particles, and the average particle size of the aggregates (d 50 ) is 30 to 500 μm.

[0157] 9A. Average particle size (d 50 ) is 3 to 50 μm.

[0158] 10A. Hexagonal boron nitride particles have an average particle size (d 50 ) . The sheet of any one of the preceding exemplary embodiments of A, comprising non-agglomerated platelet-shaped hexagonal boron nitride particles having a diameter of 100 mm.

[0159] 11A. A sheet according to any one of the preceding exemplary embodiments of A, wherein the platelet-shaped hexagonal boron nitride particles have an aspect ratio of at least 5.

[0160] 12A. The sheet of any one of the preceding exemplary embodiments of A, wherein the composite material comprises at least 80 weight percent and up to 98 weight percent hexagonal boron nitride particles, based on the total weight of the composite material.

[0161] 13A. A sheet according to any one of the exemplary embodiments of A above, wherein the composite material comprises at least 2 weight percent and at most 20 weight percent polymer, based on the total weight of the composite material.

[0162] 14A. The sheet of any one of the preceding exemplary embodiments of A, wherein the composite material further comprises 0.1 to 10 wt. % mineral oil, based on the total weight of the composite material.

[0163] 15A. A sheet according to any one of the exemplary embodiments of A above, wherein the polymer is selected from the group consisting of polyurethane, polyester, polyamide, polyether, polycarbonate, polyimide, polysulfone, polyethersulfone, polyphenylene oxide, polyacrylate, polymethacrylate, polyacrylonitrile, polyolefin, styrene, styrenic copolymer, _, chlorinated polymer, fluorinated polymer, or copolymer of ethylene and chlorotrifluoroethylene, and combinations thereof.

[0164] 16A. Polymer is 5 x 10 4 ~1×10 7 The sheet of any one of the exemplary embodiments of A above, wherein the sheet is an ultra-high molecular weight polyethylene having a number average molecular weight in the range of g / mol.

[0165] 17A. The sheet of any one of the preceding exemplary embodiments of A, wherein the composite material has a porosity of up to 40%.

[0166] 18A. The sheet of any one of the preceding exemplary embodiments of A, wherein the composite material has a porosity of 0.5 to 40%.

[0167] 19A. The sheet of any one of the preceding exemplary embodiments of A, wherein the composite material has a porosity of 2-30%.

[0168] 20A. The sheet of any one of the preceding exemplary embodiments of A, wherein the sheet has a dielectric loss tangent of less than 0.009 at 5.2 GHz.

[0169] 21A. A sheet according to any one of the preceding exemplary embodiments of A, wherein the sheet has a dielectric constant of up to 5.0 at 5.2 GHz.

[0170] 22A. A sheet according to any one of the preceding exemplary embodiments of A, wherein the through-thickness thermal conductivity of the sheet is greater than the in-plane thermal conductivity of the sheet.

[0171] 23A. The sheet of any one of the preceding exemplary embodiments of A, wherein the composite material does not contain fibers.

[0172] 24A. The sheet of any one of the preceding exemplary embodiments of A, wherein the sheet has a Shore D hardness of 30 to 150.

[0173] 25A. The sheet of any one of the preceding exemplary embodiments of A, wherein the sheet has a thickness of 0.01 mm to 6 mm.

[0174] 1B. A method for producing a sheet according to any one of the exemplary embodiments of A above, comprising: providing hexagonal boron nitride particles comprising a polymer, a solvent, and platelet-shaped hexagonal boron nitride particles; combining a polymer, a solvent, and hexagonal boron nitride particles to form a suspension of hexagonal boron nitride particles in a polymer solvent solution, wherein the polymer in the polymer solvent solution has a melting point and the solvent has a boiling point, and the step of combining the polymer, the solvent, and the hexagonal boron nitride particles is performed at a temperature above the melting point of the polymer in the polymer solvent solution and below the boiling point of the solvent; forming the suspension into a film, the platelet-shaped hexagonal boron nitride particles being oriented in a direction parallel to the plane of the film; Inducing phase separation of the polymer from the solvent; removing at least a portion of the solvent from the film to obtain a porous film; Optionally, compressing the porous film to obtain a densified film; laminating multiple films, either porous or densified, one after the other to obtain a film laminate; pressing the film laminate to obtain a bonded film laminate; and c) slicing a sheet from the bonded film stack in a direction perpendicular to the plane of the laminated film layers.

[0175] 2B. A method for producing a sheet according to any one of the exemplary embodiments of A above, comprising: providing hexagonal boron nitride particles comprising a polymer, a solvent, and platelet-shaped hexagonal boron nitride particles; combining a polymer, a solvent, and hexagonal boron nitride particles to form a slurry, the slurry being a suspension of polymer and hexagonal boron nitride particles in a solvent, the polymer having a melting point and the solvent having a boiling point, and the step of combining the polymer, the solvent, and the hexagonal boron nitride particles is performed at a temperature below the melting point of the polymer and below the boiling point of the solvent; forming the slurry into a film, wherein the platelet-shaped hexagonal boron nitride particles are oriented in a direction parallel to the plane of the film; heating the film in an environment that retains at least 90 weight percent of the solvent in the film, based on the weight of the solvent in the film, to solubilize at least 50 weight percent of the polymer in the solvent, based on the total weight of the polymer; Inducing phase separation of the polymer from the solvent; removing at least a portion of the solvent from the film to obtain a porous film; Optionally, compressing the porous film to obtain a densified film; laminating multiple films, either porous or densified, one after the other to obtain a film laminate; pressing the film laminate to obtain a bonded film laminate; and c) slicing a sheet from the bonded film stack in a direction perpendicular to the plane of the laminated film layers.

[0176] 3B. The method of Exemplary Embodiment 1B or Exemplary Embodiment 2B, wherein the polymer has a melting point and the step of inducing phase separation occurs below the melting point of the polymer.

[0177] 4B. The method of any one of the preceding exemplary embodiments of B, further comprising the step of heating the film laminate before pressing the film laminate.

[0178] 5B. The method of any one of the preceding exemplary embodiments of B, wherein the step of pressing the film laminate is carried out at a temperature of at least 110°F.

[0179] 6B. The method of any one of the preceding exemplary embodiments of B, further comprising heating the bonded film stack before slicing the sheets from the bonded film stack.

[0180] 7B. The method of any one of the preceding exemplary embodiments of B, wherein the step of pressing the film laminate is carried out under a pressing pressure of at least 2.0 MPa.

[0181] 8B. The method according to any one of the preceding exemplary embodiments of B, wherein the step of pressing the film stack is performed in the pressing direction while constraining the film stack in a first direction perpendicular to the pressing direction.

[0182] 9B. A method according to any one of the exemplary embodiments of B above, wherein the step of pressing the film laminate is performed in the pressing direction while constraining the film laminate in a first direction perpendicular to the pressing direction and in a second direction perpendicular to the pressing direction, the first direction being perpendicular to the second direction. [Example]

[0183] Test Method Airflow resistance test Air resistance was measured using an air permeability tester (obtained as Model 4110 from Gurley Precision Instruments, Troy, NY, US) with a timer (obtained as Model 4320 from Gurley Precision Instruments). The sample was clamped in the tester. The timer and photo eye were reset, the cylinder was released, and the sample was subjected to a constant force (1215 N / m) of 4.88 inches (12.4 cm) of water. 2 ) in 1 square inch (6.5 cm 2 Air was passed through a 50cm circle. 3 The time it took for the air to pass through was recorded.

[0184] Bubble Point Pressure Test Bubble point pressure is a commonly used technique for characterizing the largest pores in porous membranes. A 47 mm diameter disk was cut and the sample was immersed in 100% isopropyl alcohol (IPA) to fully fill and wet the sample's pores. The wet sample was then placed in a holder (47 mm, stainless steel holder part #2220, manufactured by Pall Corporation, Port Washington, NY, USA). The pressure above the sample was slowly increased using a pressure controller, and the gas flow below was measured using a gas flow meter. The pressure at which there was a significant increase in flow from the baseline flow rate was recorded. This was reported as the bubble point pressure (pounds per square inch (psi)). This technique is a modification of ASTM F316-03 (2006), "Standard Test Methods for Pore Size Characteristics of Membrane Filters by Bubble Point and Mean Flow Pore Test," and includes an automated pressure controller and flow meter to quantify when the bubble point pressure was reached. The pore size was calculated according to ASTM using the following formula: Threshold pore size (µm) = (surface tension in dynes / cm x 0.415) / (pressure in psi)

[0185] A factor of 0.415 was included because pressure was in units of psi. For 100% isopropyl alcohol, a surface tension of 21.7 dynes / cm was used.

[0186] Density and Porosity Testing Unless otherwise noted, the density of the samples was calculated using a method similar to ASTM F-1315-17 (2017), "Standard Test Method for Density of a Sheet Gasket Material," by cutting a 47 mm diameter disk, weighing the disk on an analytical balance of suitable resolution (typically 0.0001 gram), and measuring the thickness of the disk with a thickness gauge (obtained as Model 49-70 from Testing Machines, Inc., New Castle, DE, US) with a dead weight of 7.3 psi (50.3 KPa) and a 0.63 inch (1.6 cm) diameter flat die, a dwell time of approximately 3 seconds, and a resolution of ±0.0001 inch. The density was then calculated by dividing the mass by the volume calculated from the thickness and diameter of the sample. Using the known densities and weight fractions of the composite's components, the theoretical density of the composite was calculated using the rule of mixtures. Using the theoretical and measured densities, the porosity was calculated as follows: Porosity=[1-(measured density / theoretical density)]×100

[0187] For some samples, the density was measured using the Archimedes density method due to the uneven surface created by the bandsaw cut. The density of these samples was measured using an analytical balance (obtained from Mettler Toledo (Schweiz) GmbH, Im Langacher 44, 8608 Griefensee, Switzerland, model MS1003TS-C012187274). A glass container (similar to a beaker) was placed on the balance and filled with distilled water until it was at least three-quarters full. A sample pan with a basket attached to the bottom was placed on top of the glass container so that the basket was completely submerged, and both the pan and basket were attached to the balance to measure their mass. The balance was zeroed, and a sample approximately 1 inch x 1 inch x 1 / 2 inch in size was placed on the top pan and its mass in air was measured. This data was then saved, and the sample was placed in the basket below the pan so that its mass could be measured when submerged in water. The difference in mass between the samples when dry and when submerged in water, and the density of distilled water at 22°C is 0.99777 g / cm 3 was used to calculate the density of the blocks.

[0188] Thermal Conductivity Test Direct thermal diffusivity measurements were performed using the flash analysis method according to ASTM E1461 (2013) using a light flash thermophysical property analyzer (obtained from Netzsch Instruments North America LLC, Boston, MA, US, as "HYPERFLASH LFA 467"). Each sample set included a reference sample (obtained from Poco Graphite, Decatur, TX, US, under the trade name "AXM-5Q POCO GRAPHITE") to serve as a control for the diffusivity measurements. The light impingement and detection sides of the sample were coated with a layer of sprayed graphite (three sprays from a distance of approximately 5 inches with graphite spray obtained from Miracle Power Products Corporation, Cleveland, OH, USA, under the trade name "DGF 123 DRY GRAPHITE FILM SPRAY") to normalize the surface permeability and absorptivity for the sample being tested. Sample thickness was measured with a hand caliper (Fisher Scientific) in five different areas of the sample disk, and the average of these measurements was calculated. The thickness was used to calculate the geometric density of the sample. In a single measurement, called a "shot," a short-duration pulse of light (xenon flash lamp, 230 V, 15 microsecond duration) was impinged on one side of the sample, as measured by the voltage on the InSbIr detector, and a thermogram (time trace of the measured temperature) was recorded on the other side of the sample. Thermal diffusivity was measured in the thickness direction using a Cowan Plus Pulse The heat capacity was calculated from fitting the thermograms to a correction model and an anisotropic model for the in-plane (the anisotropic model used for the in-plane thermal diffusivity takes into account the through-thickness data). Heat capacity was calculated by differential scanning calorimetry (DSC) using a DSC instrument (obtained from TA Instruments, New Castle, DE, US, under the trade designation "Q2000 DSC") according to ASTM E1269 (2011) "Quasi-isothermal modulated DSC." Sapphire was used as the DSC reference.The diffusivity through the thickness was calculated using the Cowan method plus a finite pulse width correction, and the diffusivity in the in-plane direction used an anisotropic model with the aid of software (obtained under the trade name "Proteus" from Netzsch, Selb, Germany). Samples with a diameter of 1 inch were used for the measurements. Three shots were taken at 25°C for each sample. The measured density (ρ) (geometry from a 2.54 cm (1 inch) disk), specific heat capacity (c), and the like were used. p ) (by differential scanning calorimetry) and (α) the diffusivity to give the thermal conductivity: k(W / (m×K))=ρ(g / cm3)×c P (J / K / g)×α(mm 2 / s)

[0189] Hardness measurement (Shore D) The Shore Durometer hardness of the samples was measured according to ASTM D2240-15 using the D scale. Testing was performed under ambient laboratory conditions at 23°C and less than 20% relative humidity. Reported measurements were from laminated bonded blocks and reported as the average of four measurements on the scraped surface parallel to the laminate plane.

[0190] Dielectric property measurement (split post dielectric resonator measurement at 5.2GHz) All dielectric properties were measured at 5.2 GHz using split-post dielectric resonators (SPDRs) according to the IEC 61189-2-712 standard. Each 1 mm-thick sample was inserted between two fixed dielectric resonators. The resonant frequency and quality factor of the posts are affected by the presence of the specimen, allowing for direct calculation of the complex permittivity (dielectric constant and dielectric loss). The geometry of the split-post dielectric resonator fixture used for the measurements was constructed at QWED (Warsaw, Poland) and purchased in collaboration with the Warsaw University of Technology under Professor Jerzy Krupka. This 5.2 GHz resonator operates in the TE01δ mode, with only the azimuthal electric field component remaining continuous at the dielectric interface. The split-post dielectric resonators measure the permittivity in the plane of the specimen. Loop coupling (critically coupled) was used in each of these dielectric resonator measurements. This 5.2 GHz SPDR measurement system was coupled with a Keysight VNA (Vector Network Analyzer Model PNA 8364C 10 MHz to 50 GHz). Calculations were performed using commercially available analysis software written by Professor Jerzy Krupka and facilitated by Keysight's N1500A dielectric measurement software suite.

[0191] Orientation index measurement The orientation index is determined by X-ray diffraction. To do this, the ratio of the intensities of the (100) and (002) reflections of hexagonal boron nitride (hBN) measured in the X-ray diffractogram of a sheet sample is determined and divided by the corresponding ratio for an ideal, unoriented, or isotropic hBN sample. This ideal, or reference, intensity ratio can be determined from the International Center for Diffraction Data (ICDD) data (2020) Powder Diffraction Pattern (PDF) #01-073-2095 and is 0.147. The theoretical peak positions for the (002) and (100) reflections are 26.7° and 41.6°, respectively. The peak intensities of the (002) and (100) reflections are measured from the peak areas at these positions.

[0192] For peak intensity measurements of the (002) and (100) reflections, samples were cut and loaded onto a zero-background silicon sample holder. Reflection geometry data were collected in the form of survey scans using a PANalytical Empyrean vertical diffractometer, copper Ka radiation, and a PIXcel-3D detector (1D mode with 255 channels or a 3.35° aperture) for scattered radiation. The X-ray source and detector were positioned in a circle with a radius of 240.00 mm. The diffractometer was equipped with a 0.04 rad solar array on both the incident and diffracted beam sides, a mask 20 and Ni filter on the incident side, a programmable divergence slit at a sample distance of 140.00 mm to control the exposure length at the sample to 5.0 mm, a 2.00 mm high receiving slit, and a programmable anti-scatter slit to control the observation length to 2.0 mm. Survey scans were performed from 5 to 80° (2q) using settings of a 0.04° step size and 1200 s dwell time. X-ray generator settings of 40 kV and 40 mA were used.

[0193] The orientation index (OI) can be determined from the measured peak intensities of the (002) and (100) reflections using the following equation:

number

[0194] Examples 1 to 4 (EX1 to EX4) Ultra-high molecular weight polyethylene (UHMWPE) powder (obtained under the trade designation "GUR-2126" from Celanese Corporation, Irvine, TX, USA) was metered into the feed funnel of a twin-screw extruder (25 mm co-rotating twin-screw extruder, Berstorff, Germany) at 200 rpm and 93°C from a powder feeder (KT20, Coperion K-Tron, Stuttgart, Germany) at the rate shown in Table 1. Mineral oil (Kaydol White Mineral Oil from Brenntag Great Lakes, LLC) was pumped into open barrel zone 2 of the extruder at 93°C using a gear pump (Zenith Pumps, Monroe, NC, USA) and a Coriolis mass flowmeter (Micro Motion Mass Flowmeter, Emerson Electric Co, St. Louis, MO, USA) at the rate shown in Table 1, mixed, and heated to 204°C to melt the UHMWPE into the mineral oil. Finally, hexagonal boron nitride particles (BN; grades shown in Table 1, 3M Company, St. Paul, MN, USA) were fed from a powder feeder into a side stuffer (Century Extrusion, Travers City, MI, USA) connected to zone 4 of a twin-screw extruder at 204 °C at 100 rpm and incorporated into the melt. The extruder mixed, dispersed, and increased the temperature of the melt to create a stable mixture (i.e., a suspension). The mixture was then extruded through a drop die (6-inch (15.24 cm), Wide Ultraflex U40, Nordson Extrusion Dies LLC, Chippewa Falls, WI, USA) at 180 °C onto a smooth casting roll at 60 °C at the rate shown in Table 1 and quenched to form a film. Upon quenching, the ultra-high molecular weight polyethylene phase-separated from the suspension to form a phase-separated porous polymer network connecting the hexagonal boron nitride particles with the void-filling mineral oil. The mineral oil in the film was then extracted with 3M NOVEC 72DE (3M Company, St. Paul, MN, US) by passing the film through a countercurrent extraction bath at a rate of 10 fpm (feet per minute). The bath, with a total capacity of 300 gallons, was divided into seven tanks.The exchange rate of the 3M NOVEC 72DE bath was 52 gallons per hour. The film was then passed through a dryer at 83°C to evaporate and recover the NOVEC 72DE, resulting in a porous film. Ten to 50 yards of porous film were produced for each sample. [Table 1]

[0195] CFP 012P has an average aggregate size (d 50 ) and an average particle size (d 50 ), available from 3M Company, St. Paul, MN, USA, under the trade designation "3M™ Boron Nitride Powder Coolant Filler Platelet CFP 012P."

[0196] CFF 500-15 has an average aggregate size (d 50 ) and an average particle size (d 50 ), available from 3M Company, St. Paul, MN, USA, under the trade name "3M™ Boron Nitride Powder Coolant Filler Flake CFF 500-15."

[0197] CFA 250S produced an average aggregate size (d 50 ) (available from 3M Company, St. Paul, MN, USA under the trade designation "3M™ Boron Nitride Powder Coolant Filler Agglomerate CFA 250S").

[0198] The test results of the obtained porous film are shown in Table 2. [Table 2] *) nm = not measured

[0199] The resulting porous film was then calendered to reduce porosity and improve thermal conductivity by passing a 3-inch wide sample through two smooth, 10-inch diameter horizontal calender rolls set at a force of 4000 pli (pounds per linear inch) at 4 fpm.

[0200] The test results of the resulting densified film are shown in Table 3. [Table 3]

[0201] The resulting densified film was then cut with scissors into 1 inch by 2 inch strips, which were laminated between two release liner films and pressed in a hydraulic press heated to 149°C (300°F) with a press force gradually increased to 5000 lbf over a period of 5 minutes, using 0.580 inch shims on both sides of the laminate to keep the laminate vertical. The number of laminated strips is shown in Table 4. The resulting pressed film laminate, a bonded block (or bonded film laminate) made from the laminated film strips, was removed from the hydraulic press and allowed to cool to room temperature (23°C). After removal, the sheet was cut using a razor blade to sever all of the film layers. In the resulting cut sheet, the hexagonal boron nitride particles are oriented perpendicular to the plane of the sheet.

[0202] The test results of the obtained sheet are shown in Table 4. [Table 4]

[0203] Example 5 (EX5) For Example 5, a densified film was prepared as described in Example 1, except that extrusion was carried out at 193°C (380°F) instead of 180°C, an 8-inch drop die was used for extrusion instead of a 6-inch, countercurrent extraction was carried out at a rate of 2 fpm, and the formulation used was as shown in Table 5. [Table 5]

[0204] CFA 50 is a 50 μm protective screening and 20 μm mean particle size (d 50 ), available from 3M Company, St. Paul, MN, USA, under the trade designation "3M™ Boron Nitride Powder Coolant Filler Agglomerate CFA 50."

[0205] Test results for densified films made according to the procedure described in Example 1 are shown in Table 6. [Table 6]

[0206] The resulting densified film was then cut with scissors into 2-inch by 2-inch strips, which were laminated between two release liner films and pressed in a hydraulic press heated to 149°C (300°F) with a press force gradually increasing to 2500 lbf over 2.5 minutes, using 1.375-inch shims on both sides of the laminate to keep the laminate vertical. The number of laminated strips is shown in Table 7. The resulting pressed film laminate, a bonded block (or bonded film laminate) made from the laminated film strips, was removed from the hydraulic press and allowed to cool to room temperature (23°C). The bonded block was then placed in a laboratory oven at 149°C for 10 minutes. The oven-warmed bonded block was then quickly returned to a hydraulic press heated to 176.6°C (350°F) and compressed by gradually increasing the press force to 1700 lbf over 3 minutes. The bonded block was then removed from the hydraulic press and allowed to cool to room temperature (23°C), after which the sheet was cut using a skiving knife to separate all of the film layers, leaving a sheet in which the hexagonal boron nitride particles were oriented perpendicular to the plane of the sheet.

[0207] The test results of the obtained sheet are shown in Table 7. [Table 7]

[0208] Examples 6 to 8 (EX6 to EX8) For Examples 6-8, porous films were prepared using the composition and preparation method described in Example 5, except that the casting roll speed was 3 fpm. After the porous films were obtained, no calendering step was performed. The porous films were then cut into 1-inch x 1-inch squares with scissors. To stack and press the squares, i.e., to stack multiple layers of porous film and press the film laminate, a steel mold was used to constrain the laminate in the x and y directions. The steel mold had a cavity 1.0625 inches wide, 1.0625 inches long, and 1.5 inches high, and a top plunger. The mold was preheated by placing it in a 300°F (149°C) oven for 30 minutes. The mold was removed from the oven, and the 1-inch x 1-inch squares were laminated into the mold to a height of 1.4 inches. Release liners were placed on the top and bottom of the laminate. The top plunger was inserted, and the mold and laminated film squares were placed in a 300°F (149°C) oven for 15 minutes. The mold and film laminate were then quickly removed from the oven and placed in a hydraulic press heated to 350°F (176.6°C) and pressed by gradually increasing the force over a period of 3 minutes to the values ​​shown in Table 8. The mold was then removed from the hydraulic press, opened, and additional film squares were added. The process of heating, pressing, and adding additional squares was then repeated three times until the laminate was approximately 1 inch high. The resulting pressed film laminate was a bonded block (or bonded film laminate) made from the laminated film squares. After being removed from the hydraulic press and allowed to cool to room temperature (23°C), the sheet was cut using a band saw to cut through all of the film layers. In the resulting cut sheet, the hexagonal boron nitride particles were oriented perpendicular to the plane of the sheet.

[0209] The results are shown in Table 8. [Table 8]

[0210] As can be seen from Table 8, the through thickness thermal conductivity of the sheet of Example 8 is significantly higher than the porosity of the sheet of Example 5, while the porosity of the sheet of Example 8 is similar to that of the sheet of Example 5. This can be explained by the higher pressure used in pressing the film stack, resulting in increased layer-to-layer, i.e., particle-to-particle contact of the hexagonal boron nitride particles between the original individual adjacent film layers in the bonded film stack formed during pressing.

[0211] Example 9 (EX9) For Example 9, a porous film was prepared as described for Example 7. After obtaining the porous film, no calendering step was performed. The porous film was then cut into 1.5 inch x 1.5 inch squares with scissors. To stack and press the squares, i.e., to stack multiple layers of porous film and press the film laminate, a steel mold was used to constrain the laminate in the x and y directions. The steel mold had a cavity 1.625 inches wide, 1.625 inches long, and 2.625 inches high, with a 1.25 inch high top plunger. The mold was preheated by placing it in a 300°F (149°C) oven for 60 minutes. The mold was removed from the oven, and the 1.5 inch x 1.5 inch squares were stacked into the mold to a height of 1.4 inches. Release liners were placed on the top and bottom of the laminate. The top plunger was inserted into the mold. The mold and laminated film squares were placed in a 300°F (149°C) oven for 15 minutes. The mold and laminate were then quickly removed from the oven and placed in a hydraulic press heated to 350°F (176.6°C) and pressed by gradually increasing the pressure over a period of 3 minutes to the values ​​shown in Table 9. The mold was then removed from the hydraulic press, opened, and additional film squares were added. The process of heating, pressing, and adding additional squares was then repeated three times until the laminate reached a height of approximately 1.5 inches. The resulting pressed film laminate, a bonded block (or bonded film laminate) made from the laminated film squares, was removed from the hydraulic press and allowed to cool to room temperature (23°C). The sheet was then cut using a band saw to sever all of the film layers. In the resulting cut sheet, the hexagonal boron nitride particles are oriented perpendicular to the plane of the sheet.

[0212] The results are shown in Table 9. [Table 9]

[0213] Examples 10 and 11 (EX10 and EX11) A plastic mixing cup (obtained under the trade name "MAX 100 CUP," both manufactured by FlackTek, Inc., Landrum, SC, US) for a Speed ​​Mixer (obtained under the trade name "SPEEDMIXER DAC 150.1 FV") was filled with ultra-high molecular weight polyethylene (UHMWPE) powder (obtained under the trade name "GUR-2126" from Celanese Corporation, Irvine, TX, US), paraffin (obtained under the trade name "ISOPAR G" from Brenntag Great Lakes, Inc., Wauwatosa, WI, US), and hexagonal boron nitride powder (grades shown in Table 10, 3M Company, St. Paul, MN, US) in the amounts shown in Table 10. The UHMWPE, paraffin, and hexagonal boron nitride powder were mixed in the Speed ​​Mixer at 1000 rpm for 1 minute, followed by 2500 rpm for 30 seconds. The resulting slurry was then mixed by hand with a wooden tongue depressor to remove material from the corners and sides of the cup and mixed a second time at 1000 rpm for 1 minute followed by 2500 rpm for 30 seconds. [Table 10]

[0214] CPF 007HS has an average particle size (d 50 ) and high surface area boron nitride platelets with a controlled top size of 50 μm (available from 3M Company, St. Paul, MN, USA under the trade name "3M™ Boron Nitride Powder Coolant Filler Platelets CFP 007HS").

[0215] After mixing, the slurry was applied to a 3 mil (75 micrometer) polyester (PET) liner at room temperature (23°C) using a tongue depressor, and then another 3 mil (75 micrometer) PET liner was applied on top of the slurry to sandwich it in. The slurry was then spread between the PET liners using a notch bar set at a gap of 30 mil (762 micrometer) to match the thickness of the wet coating (not including the liner).

[0216] The sandwiched formed slurry was placed on an aluminum tray and placed in an oven at 150°C (302°F) for 5 minutes to activate (i.e., allow the UHMWPE to dissolve in the solvent and form a single phase). The tray with the activated sandwiched formed slurry was removed from the oven, and the sandwiched formed slurry and liner were placed on a granite block and air-cooled to ambient temperature (approximately 23°C), forming a solvent-filled (i.e., paraffin-filled) porous film sandwiched between two liners. The top liner was removed, exposing the porous film to air. The porous film on the PET liner on the tray was inserted into an oven at 100°C (212°F) for 45 minutes to evaporate the paraffin. After evaporation of the paraffin, the porous film on the PET liner was removed from the oven and allowed to cool to ambient temperature (23°C), and then the liner was removed to yield a porous film (i.e., a porous polymer network containing hexagonal boron nitride particles).

[0217] After obtaining the porous film, no calendering step was performed. The resulting porous film was then cut into 1 inch x 1 inch squares. To stack and press the squares, i.e., to stack multiple layers of porous film and press the film laminate, a steel mold was used to constrain the laminate in the x and y directions. The steel mold had a cavity 1.0625 inches wide, 1.0625 inches long, and 1.5 inches high, and a top plunger. The mold was preheated by placing it in a 300°F (149°C) oven for 30 minutes. The mold was removed from the oven, and the 1 inch x 1 inch squares were laminated into the mold to a height of 1.4 inches. Release liners were placed on the top and bottom of the laminate. The top plunger was inserted, and the mold and laminated film squares were placed in a 300°F (149°C) oven for 15 minutes. The mold and film laminate were then quickly removed from the oven and placed in a hydraulic press heated to 350°F (176.6°C) and pressed by gradually increasing the pressure to 2000 lbf (corresponding to a pressing pressure of 2000 pounds per square inch (13.8 MPa)) over a period of 3 minutes. The mold was then removed from the hydraulic press, opened, and additional film squares were added. The process was then repeated three times until the laminate was approximately 1 inch high. The resulting pressed film laminate, a bonded block (or bonded film laminate) made from the laminated film squares, was removed from the hydraulic press and allowed to cool to room temperature (23°C). After removal, the sheet was cut using a band saw to cut through all of the film layers. In the resulting cut sheet, the hexagonal boron nitride particles were oriented perpendicular to the plane of the sheet.

[0218] The test results of the obtained sheet are shown in Table 11. [Table 11]

[0219] Comparative Examples 1 to 3 (CEX1 to CEX3) Comparative Examples 1-3 were made using silicone at the same volume percent loading of hexagonal boron nitride particles as Examples 10-12. A plastic mixing cup (obtained under the trade designation "MAX 100 CUP," both from FlackTek, Inc., Landrum, SC, US) for a Speed ​​Mixer (obtained under the trade designation "SPEEDMIXER DAC 150.1 FV") was filled with two-part silicone (obtained under the trade designation "Sylgard 184" from Dow Chemical Co., Midland, MI, US) and hexagonal boron nitride particles (grades shown in Table 12, 3M Company, St. Paul, MN, US) in the amounts shown in Table 12. The two-part silicone and hexagonal boron nitride particles were mixed in the Speed ​​Mixer at 3500 rpm for 30 seconds. [Table 12]

[0220] The resulting slurry was then placed between two PET release liners and pressed using a 0.576 inch shim on a hydraulic press heated to 130°C to attempt to form a film. The sample was removed from the hydraulic press, allowed to cool to room temperature (23°C), and the release liners were removed to yield a silicone / boron nitride sample.

[0221] Test results for the silicon / boron nitride samples are shown in Table 13. [Table 13]

[0222] For Comparative Example 1, when attempts were made to form a film, the resulting sample was too brittle to cut strips from it and to form a film laminate without the layers crumbling. The sample was dusty around the edges and easily broke when pressure was applied.

[0223] For Comparative Example 2, when an attempt was made to form a film, the resulting sample looked like a pile of powder. It was not possible to form a laminate of film layers.

[0224] For Comparative Example 3, the resulting film sample was then cut into 2-inch by 2-inch squares with a razor. A thin layer of two-part silicone was applied to the top of the squares using a foam tip applicator, and six film layers were laminated together to form a block with silicone between each layer. The block was then placed between 0.575-inch shims in a hydraulic press heated to 130°C and pressed for 30 minutes to cure the silicone. The bonded block was then removed from the hydraulic press and allowed to cool to room temperature (23°C), after which the sheet was cut using a band saw to sever all of the layers.

[0225] The test results of the obtained sheet are shown in Table 14. [Table 14]

[0226] Table 14 shows that the through-thickness thermal conductivity of Comparative Example 3 is lower than that of Example 11, although both samples had a similar content of hexagonal boron nitride particles (about 70 wt%). Comparative Examples 1 and 2: Film laminates could not be made and therefore the sheets could not be sliced ​​perpendicular to the plane of the laminated film layers.

[0227] Examples 12 and 13 (EX12 and EX13) For Examples 12 and 13, porous films were prepared according to the procedure described for Examples 10 and 11, except that the formulations shown in Table 15 were used. The mineral oil was obtained from Brenntag Great Lakes, LLC under the trade name "Kaydol White Mineral Oil." The paraffin-filled porous film was evaporated (100°C, 45 minutes) to yield a porous film containing mineral oil in the porous polymer network. [Table 15]

[0228] CFA 150 has an average aggregate size (d 50 ), available from 3M Company, St. Paul, MN, USA, under the trade designation "3M™ Boron Nitride Powder Coolant Filler Agglomerate CFA 150."

[0229] The resulting porous film was then calendered to reduce porosity and improve thermal conductivity by passing a 3-inch wide sample through two smooth, 10-inch diameter horizontal calender rolls at 4 fpm set at the force shown in Table 16.

[0230] Test results for the resulting densified films are shown in Table 16. [Table 16]

[0231] The resulting densified film was then cut with scissors into 1.5 inch x 1.5 inch strips, which were laminated between two release liner films and pressed in a hydraulic press heated to 149°C (300°F) with a press force gradually increasing to 2500 lbf over 2.5 minutes, using 1.375 inch shims on both sides of the laminate to limit compression and keep the laminate vertical. The number of laminated strips is shown in Table 17. The resulting pressed film laminate, a bonded block (or bonded film laminate) made from the laminated film strips, was removed from the hydraulic press and allowed to cool to room temperature (23°C). The bonded block was then placed in a laboratory oven at 149°C for 10 minutes. The oven-warmed bonded block was then quickly returned to the hydraulic press heated to 176.6°C (350°F) and compressed by gradually increasing the press force to 1700 lbs over 3 minutes. The bonded block was then removed from the hydraulic press and allowed to cool to room temperature (23°C), after which the sheet was cut using a band saw to cut through all of the film layers, with the hexagonal boron nitride grains oriented perpendicular to the plane of the sheet.

[0232] The test results of the obtained sheet are shown in Table 17. [Table 17] *) nm = not measured

[0233] The hardness of the samples with mineral oil in the final sheet is lower than the hardness of the samples without mineral oil in the final sheet.

[0234] Example 14 (EX14) For Example 14, a porous film was prepared using the same composition and preparation method as in Example 13. After the porous film was obtained, no calendering step was performed. The resulting porous film was then cut into 1 inch x 1 inch squares. To laminate the squares, i.e., to laminate multiple layers of porous film, a steel mold was used to constrain the laminate in the x and y directions. The steel mold had a cavity 1.0625 inches wide, 1.0625 inches long, and 1.5 inches high, and a top plunger. The mold was preheated by placing it in a 300°F (149°C) oven for 30 minutes. The mold was removed from the oven, and the 1 inch x 1 inch squares were laminated into the mold to a height of 1.4 inches. Release liners were placed on the top and bottom of the laminate. The top plunger was inserted, and the mold and laminated film squares were placed in a 300°F (149°C) oven for 15 minutes. The mold and laminate were then quickly removed from the oven and placed in a hydraulic press heated to 350°F (176.6°C) and pressed by gradually increasing the pressure to 2000 lbf (corresponding to a pressing pressure of 2000 pounds per square inch (13.8 MPa)) over a period of 3 minutes. The mold was then removed from the hydraulic press, opened, and additional film squares were added. The process was then repeated three times until the laminate was approximately 1 inch high. The resulting pressed film laminate, a bonded block (or bonded film laminate) made from the laminated film squares, was removed from the hydraulic press and allowed to cool to room temperature (23°C). After removal, the sheet was cut using a band saw to cut through all of the film layers. In the resulting cut sheet, the hexagonal boron nitride particles were oriented perpendicular to the plane of the sheet.

[0235] The test results of the obtained sheet are shown in Table 18. [Table 18]

[0236] Example 15 (EX15) Example 15 was prepared by charging 0.4561 g of ultra-high molecular weight polyethylene (UHMWPE) powder, 12.6135 g of mineral oil (obtained under the trade name "Kaydol White Mineral Oil" from Brenntag Great Lakes, LLC), 16.7774 g of hexagonal boron nitride particles (obtained under the trade name "3M™ Boron Nitride Powder Coolant Filler Agglomerate CFA 50" from 3M Company, St. Paul, MN, USA), and 1.1309 g of elastomer (obtained under the trade name Krayton 1645 from Krayton Corporation, Houston, TX) to the 350°F (176.6°C) bowl of a mixer (Brabender CW DR-2051, Brabender GmbH & Co. KG, Duisburg, Germany). The bowl was mixed at 50 rpm for 5 minutes to melt the UHMWPE and mix the ingredients.

[0237] The molten suspension was removed from the bowl with a tongue depressor and placed between two heat-stable release liners. It was then pressed into a hydraulic press heated to 350°F (176.6°C) with 61.5 mil shims placed on both sides of the laminate between the release liners to limit compression, and the force gradually increased to 3000 lbf over 5 minutes to form a film. The film was then removed from the hydraulic press and placed between cooling plates for 5 minutes to rapidly cool to room temperature (23°C).

[0238] The liner was removed and the film sample was washed three times in a dish of excess Novec 72DE with a 10-minute soak time, after which the solvent was drained and replaced. Following the final wash, the sample was allowed to dry in a fume hood at room temperature (23°C) for at least 1 hour.

[0239] The test results of the obtained porous film are shown in Table 19. [Table 19]

[0240] The resulting porous film was cut into 3 inch wide film strips, placed between two release liners, and then calendered at 1000 pli and 5 fpm to densify the sample.

[0241] The test results of the resulting densified films are shown in Table 20. [Table 20]

[0242] The resulting densified film was then cut into 1 inch x 1 inch squares. To laminate the squares, i.e., to stack multiple layers of densified film, a steel die was used to constrain the laminate in the x and y directions. The steel die had a 1.0625 inch wide, 1.0625 inch long, 1.5 inch high cavity and a top plunger. The die was preheated by placing it in a 300°F (149°C) oven for 30 minutes. The die was removed from the oven, and the 1 inch x 1 inch squares were laminated into the die to a height of 1.4 inches. Release liners were placed on the top and bottom of the laminate. The top plunger was inserted, and the die and laminated film squares were placed in a 300°F (149°C) laboratory oven for 15 minutes. The mold and laminate were then quickly removed and placed on a hydraulic press heated to 176.6°C (350°F) and pressed by gradually increasing the pressure to 2000 lbf (corresponding to a pressing pressure of 2000 pounds per square inch (13.8 MPa)) over a period of 3 minutes. The mold was then removed from the hydraulic press, opened, and additional film squares were added. The process was then repeated three times until the laminate was approximately 1 inch high. The resulting pressed film laminate, a bonded block (or bonded film laminate) made from the laminated film squares, was removed from the hydraulic press and allowed to cool to room temperature (23°C). After removal, the sheet was cut using a band saw to cut through all of the film layers. In the resulting cut sheet, the hexagonal boron nitride particles were oriented perpendicular to the plane of the sheet.

[0243] The test results of the obtained sheet are shown in Table 21. [Table 21]

[0244] The hardness of the samples with elastomer in the final sheet is lower than the hardness of the samples without elastomer in the final sheet.

Claims

1. 1. A sheet comprising a composite material comprising a polymer and hexagonal boron nitride particles, the hexagonal boron nitride particles comprising platelet-shaped hexagonal boron nitride particles oriented in a direction perpendicular to the direction of a plane of the sheet, the composite material comprising at least 70 weight percent of the hexagonal boron nitride particles based on a total weight of the composite material, and the sheet having a through thickness thermal conductivity of greater than 12 W / m×K.

2. 2. The sheet according to claim 1, wherein the composite material is obtained by densifying a material comprising a porous network of the polymer.

3. 3. The sheet according to claim 1 or 2, wherein the composite material comprises at least 80 weight percent, preferably at least 85 weight percent, more preferably at least 90 weight percent, more preferably more than 90 weight percent of the hexagonal boron nitride particles, based on the total weight of the composite material.

4. The sheet according to any one of claims 1 to 3, wherein the sheet has a thickness-wise thermal conductivity of at least 15 W / m×K.

5. The sheet according to any one of claims 1 to 4, wherein the orientation index of the sheet is greater than 4.

0.

6. The sheet of any one of claims 1 to 5, wherein the composite material further comprises 0.1 to 10 wt % mineral oil, based on the total weight of the composite material.

7. 7. The sheet of any one of claims 1 to 6, wherein the polymer is selected from the group consisting of polyurethanes, polyesters, polyamides, polyethers, polycarbonates, polyimides, polysulfones, polyethersulfones, polyphenylene oxides, polyacrylates, polymethacrylates, polyacrylonitriles, polyolefins, styrenes, styrenic copolymers, styrene-based copolymers, chlorinated polymers, fluorinated polymers, copolymers of ethylene and chlorotrifluoroethylene, and combinations thereof.

8. The polymer is 5×10 4 ~1×10 7 A sheet according to any one of claims 1 to 7, which is an ultra-high molecular weight polyethylene having a number average molecular weight in the range of g / mol.

9. A sheet according to any one of the preceding claims, wherein the composite material has a porosity of up to 40%.

10. The sheet according to any one of claims 1 to 9, wherein the sheet has a Shore D hardness of 30 to 150.

11. providing hexagonal boron nitride particles comprising a polymer, a solvent, and platelet-shaped hexagonal boron nitride particles; combining the polymer, the solvent, and the hexagonal boron nitride particles to form a suspension of hexagonal boron nitride particles in a polymer solvent solution, wherein the polymer in the polymer solvent solution has a melting point and the solvent has a boiling point, and combining the polymer, the solvent, and the hexagonal boron nitride particles is performed at a temperature above the melting point of the polymer in the polymer solvent solution and below the boiling point of the solvent; forming the suspension into a film, the platelet-shaped hexagonal boron nitride particles being oriented in a direction parallel to the direction of the plane of the film; inducing phase separation of the polymer from the solvent; removing at least a portion of the solvent from the film to obtain a porous film; Optionally, compressing the porous film to obtain a densified film; laminating a plurality of the porous films or the densified films one after the other to obtain a film laminate; pressing the film laminate to obtain a bonded film laminate; and slicing a sheet from the bonded film laminate in a direction perpendicular to the plane of the laminated film layers.

12. A method for producing the sheet according to any one of claims 1 to 10, providing hexagonal boron nitride particles comprising a polymer, a solvent, and platelet-shaped hexagonal boron nitride particles; combining the polymer, the solvent, and the hexagonal boron nitride particles to form a slurry, the slurry being a suspension of the polymer and the hexagonal boron nitride particles in the solvent, the polymer having a melting point and the solvent having a boiling point, and the combining of the polymer, the solvent, and the hexagonal boron nitride particles is performed at a temperature below the melting point of the polymer and below the boiling point of the solvent; forming the slurry into a film, the platelet-shaped hexagonal boron nitride particles being oriented in a direction parallel to the plane of the film; heating the film in an environment that retains at least 90 weight percent of the solvent in the film, based on the weight of the solvent in the film, to solubilize at least 50 weight percent of the polymer in the solvent, based on the total weight of the polymer; inducing phase separation of the polymer from the solvent; removing at least a portion of the solvent from the film to obtain a porous film; Optionally, compressing the porous film to obtain a densified film; laminating a plurality of the porous films or the densified films one after the other to obtain a film laminate; pressing the film laminate to obtain a bonded film laminate; and c) slicing a sheet from the bonded film stack in a direction perpendicular to the plane of the laminated film layers.

13. 13. The method of claim 11 or 12, further comprising the step of heating the film stack prior to pressing the film stack.

14. The method of any one of claims 11 to 13, wherein the step of pressing the film laminate is carried out at a temperature of at least 110°F.

15. The method of any one of claims 11 to 14, further comprising the step of heating the bonded film stack prior to slicing sheets from the bonded film stack.

16. The method according to any one of claims 11 to 15, wherein the step of pressing the film stack is carried out under a pressing pressure of at least 2.0 MPa.

17. The method of any one of claims 11 to 16, wherein the step of pressing the film stack is performed in a pressing direction while constraining the film stack in a first direction perpendicular to the pressing direction.

18. 18. The method of any one of claims 11 to 17, wherein the step of pressing the film stack is performed in a press direction while constraining the film stack in a first direction perpendicular to the press direction and in a second direction perpendicular to the press direction, the first direction being perpendicular to the second direction.